Manufacturing method of regenerated water-absorbing resin
Patent Information
- Application Number
- JP2024021301
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-09
- Filing Date
- 2024-02-15
- Publication Date
- 2025-02-21
AI Technical Summary
【0010】 本発明によれば、使用済み吸収性物品に含まれる吸水性樹脂、吸水性樹脂製造工程中の廃棄吸水性樹脂などの本来廃棄すべき吸水性樹脂を使用して、再生吸水性樹脂、特に保水材に適した再生吸水性樹脂を製造できる。
Smart Images

Figure 2025026271000001 
Figure 2025026271000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a recycled water-absorbent resin, particularly a method for producing a recycled water-absorbent resin, particularly a water-retaining material, using a water-absorbent resin contained in a used absorbent article or a waste product from a water-absorbent resin production process. [Background technology]
[0002] Super absorbent polymers (SAP) are water-swellable, water-insoluble polymer gels. It is a water retaining agent and is used in various absorbent articles such as disposable diapers, sanitary napkins, incontinence products for adults (incontinence pads), hygiene materials (hygienic products) such as pet sheets, soil water retaining agents for agricultural and horticultural use, industrial water cutting agents, etc. For example, Patent Document 1 describes a water retaining material containing a water absorbent resin having at least one element selected from the group consisting of phosphorus, potassium and nitrogen elements inside the water absorbent resin, which does not constitute the polymer skeleton of the resin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-10303 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the water-retentive material of Patent Document 1 was not sufficient as a water-retentive material because the elements were washed away when the material absorbed water or when it rained.
[0005] On the other hand, sanitary materials such as paper diapers and sanitary napkins are the main applications of water-absorbent resins. After being used for a short period of time (at most about one day), these sanitary materials are discarded in large quantities as used absorbent articles and incinerated. On the other hand, in recent years, from the viewpoint of environmental protection, etc., attempts have been made to recycle such used absorbent articles. For example, in addition to the above-mentioned water-absorbent resin, sanitary materials contain raw materials such as pulp, nonwoven fabrics, and adhesives, and material recycling has been attempted in which these raw materials are separated from used sanitary materials and reused.
[0006] Therefore, the present invention has been made in consideration of the above circumstances, and aims to provide a technique for producing a recycled water-absorbent resin, particularly a recycled water-absorbent resin suitable for a water-retaining material, by using a water-absorbent resin that should be discarded, such as a water-absorbent resin contained in a used absorbent article or a water-absorbent resin discarded during a water-absorbent resin manufacturing process. [Means for solving the problem]
[0007] The present inventors have conducted intensive research to solve the above-mentioned problems, and as a result, have found that the above-mentioned problems can be solved by making potassium element and nitrogen element exist in a certain ratio in the skeleton of a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin manufacturing process, and have completed the present invention.
[0008] That is, the above-mentioned object can be achieved by a method for producing a regenerated water absorbent resin, comprising: treating a raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salts, potassium salts, lithium salts, magnesium salts, calcium salts and iron salts of a carboxyl group with an acidic substance; and adding a substance containing at least one element selected from the group consisting of potassium element and nitrogen element to the raw water absorbent resin treated with the acidic substance in an amount such that the substitution rate of the carboxyl group is more than 5 mol % and less than 40 mol %, thereby substituting the carboxyl group present in the raw water absorbent resin with the element.
[0009] The above object can also be achieved by a water absorbent resin composition comprising a water absorbent resin having a carboxyl group, and a part of the carboxyl group being substituted with at least one element selected from the group consisting of potassium element and nitrogen element at a substitution rate of 5 mol % or more and 100 mol % or less, and a fibrous material. Effect of the Invention
[0010] According to the present invention, a recycled water absorbent resin, particularly a recycled water absorbent resin suitable for a water retention material, can be produced by using a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin production process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] One aspect of the present invention relates to a method for producing a recycled water absorbent resin, which comprises treating a raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salt, potassium salt, lithium salt, magnesium salt, calcium salt, and iron salt of a carboxyl group with an acidic substance (acid treatment step), and adding a substance containing at least one element selected from the group consisting of potassium element and nitrogen element to the raw water absorbent resin treated with the acidic substance in an amount such that the substitution rate of the carboxyl group is more than 5 mol% and less than 40 mol% to substitute the carboxyl group present in the raw water absorbent resin with the element (substitution step). With this configuration, even when using a water absorbent resin that should be discarded, such as a water absorbent resin contained in a used absorbent article or a water absorbent resin discarded during a water absorbent resin production process, a recycled water absorbent resin, particularly a recycled water absorbent resin suitable for a water retention material, can be produced.
[0012] Another aspect of the present invention relates to a water-absorbent resin composition comprising a water-absorbent resin having carboxyl groups, and a part of the carboxyl groups being substituted with at least one element selected from the group consisting of potassium and nitrogen at a substitution rate of 5 mol % to 100 mol %, and a fibrous material. With this constitution, even when a water-absorbent resin substituted with a wider range of substituents is used, the water-absorbent resin composition can be suitably used as a water-retaining material by combining with the fibrous material.
[0013] In this specification, "a polymer having at least one salt selected from the group consisting of sodium salts, potassium salts, lithium salts, magnesium salts, calcium salts, and iron salts of a carboxyl group" is also simply referred to as "raw polymer" or "raw polymer according to the present invention". "A raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salts, potassium salts, lithium salts, magnesium salts, calcium salts, and iron salts of a carboxyl group" is also referred to as "raw water absorbent resin" or "raw water absorbent resin according to the present invention". "A substance containing at least one element selected from the group consisting of potassium element and nitrogen element" is also simply referred to as "K / N-containing substance" or "K / N-containing substance according to the present invention".
[0014] As mentioned above, used absorbent articles such as paper diapers and sanitary napkins are discarded and incinerated in large quantities. However, in recent years, from the viewpoint of environmental protection, attempts have been made to recycle such used absorbent articles, and water-retaining materials have been considered as one of the methods. In the water-absorbent resin constituting the water-retaining material described in Patent Document 1, one or more elements of phosphorus, potassium, and nitrogen are present inside the resin so as not to form a polymer skeleton. It is known that the elements are useful as fertilizers. However, it has been found that the water-retaining material of Patent Document 1 may not be effective as a fertilizer in some cases. The present inventors have conducted extensive research into the above phenomenon and have speculated that this is because the elements are not incorporated into the polymer skeleton, and therefore the elements flow out of the water-retaining material together with water when absorbing water or when it rains. For this reason, in order to suppress and prevent the outflow of the elements from the water-retaining material, it is considered that it is effective to incorporate potassium and nitrogen elements in an appropriate amount into the polymer skeleton. Further extensive research has been conducted into the incorporation of the elements. As a result, the salt of the carboxyl group of the polymer that constitutes the water-absorbing resin, which should have been discarded, was converted to a carboxyl group (-COOH) by acid treatment, and then potassium (-COOK) or nitrogen element (e.g., -COO - NH4 + ) and incorporating these elements into the polymer skeleton. However, it was found that simply incorporating the elements into the polymer skeleton does not necessarily result in sufficient plant growth (e.g., germination rate). The present inventors further investigated the above phenomenon and speculated that the substitution rate of the carboxyl group with potassium element or nitrogen element has a strong effect on plant growth (e.g., germination rate). Based on the above speculation, the substitution rate was further investigated and it was found that plant growth (e.g., germination rate) can be improved by adjusting the substitution rate to more than 5 mol% and less than 40 mol%.
[0015] It should be noted that the above is merely speculation and is not intended to limit the technical scope of the present invention.
[0016] Preferred embodiments of the present invention will be described below. Note that the present invention is not limited to the following embodiments, and can be modified in various ways within the scope of the claims. In addition, the embodiments described in this specification can be combined in any manner to form other embodiments.
[0017] In this specification, the term "(meth)acrylic" includes both acrylic and methacrylic. Thus, for example, the term "(meth)acrylic acid" includes both acrylic acid and methacrylic acid. Also, "acid (salt)" means "acid and / or its salt."
[0018] [1] Definitions of terms [1-1] Regenerated water absorbent resin The "regenerated water-absorbent resin" produced by the method of the present invention is a water-swellable water-insoluble polymer gelling agent, and refers to a conventional water-absorbent resin having a water absorption capacity of 10 to 1000 times, although it is not particularly limited thereto. More specifically, the water-absorbent resin before absorbing the liquid to be absorbed preferably satisfies the physical property of a deionized water CRC of 5 g / g or more as "water-swellability". The definition of the deionized water CRC will be described later.
[0019] The recycled water-absorbing resin includes a polymer having a carboxyl group partially neutralized with potassium or nitrogen. Specific examples of the recycled water-absorbing resin include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, cellulose-based resins, (meth)acrylate crosslinked polymers, saponified crosslinked products of (meth)acrylate-vinyl acetate copolymers, starch-acrylate graft polymers and crosslinked products thereof.
[0020] In this specification, the recycled water-absorbent resin is not limited to an embodiment in which the total amount (100 mass %) is the water-absorbent resin alone, but may be a water-absorbent resin composition containing additives and the like.
[0021] [1-2] Raw material water absorbent resin The "raw water absorbent resin" includes a polymer (raw polymer) having at least one salt selected from the group consisting of sodium salt, potassium salt, lithium salt, magnesium salt, calcium salt, and iron salt of a carboxyl group. Preferably, the raw water absorbent resin includes a polymer having a sodium salt and / or a lithium salt of a carboxyl group. More preferably, the raw water absorbent resin includes a polymer having a sodium salt of a carboxyl group.
[0022] In one embodiment of the present invention, the raw water absorbent resin has a neutralization rate of 40 mol% or more. The raw water absorbent resin preferably has a neutralization rate of 50 mol% or more and 100 mol% or less, more preferably 60 mol% or more and 90 mol% or less.
[0023] In one embodiment of the present invention, the CRC (before moisture absorption) of the raw water absorbent resin is 20 g / g or more, 25 g / g or more, 27 g / g or more, or 30 g / g or more. In one embodiment of the present invention, the CRC (before moisture absorption) of the raw water absorbent resin is 70 g / g or less, 50 g / g or less, or 45 g / g or less. The definition of CRC is as described in [1-5-1] below.
[0024] In one embodiment of the present invention, the AAP (0.3 psi) of the raw water absorbent resin is 10 g / g or more, 15 g / g or more, 20 g / g or more, 22 g / g or more, 24 g / g or more, or , 25 g / g or more. In one embodiment of the present invention, the AAP (0.3 psi) of the raw water absorbent resin is 50 g / g or less, 45 g / g or less, 40 g / g or less, 35 g / g or less, or 30 g / g or less. The definition of AAP is as described in [1-5-3] below.
[0025] [1-3] Recycled water-absorbent resin The term "recovered water-absorbent resin" refers to water-absorbent resin that should be discarded. Specifically, there are water-absorbent resins contained in used absorbent articles (for example, water-absorbent resins that have absorbed body fluids such as urine and blood in used absorbent articles) and water-absorbent resins discarded during the water-absorbent resin manufacturing process (for example, fine powder or non-standard water-absorbent resins generated during the water-absorbent resin manufacturing process).
[0026] Among these, from the viewpoint of environmental protection, it is preferable to use a water absorbent resin recovered (removed and collected) from used absorbent articles. That is, in one embodiment of the present invention, the raw water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles or waste during the water absorbent resin manufacturing process. In one embodiment of the present invention, the raw water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles containing a polymer having a sodium salt, potassium salt and / or lithium salt of a carboxyl group. In one embodiment of the present invention, the raw water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles containing a polymer having a sodium salt of a carboxyl group.
[0027] Here, "used absorbent articles" refer to sanitary materials that have been used by consumers and have absorbed bodily fluids such as urine and blood. Examples of sanitary materials include paper diapers, sanitary napkins, and adult incontinence products (incontinence pads). Products similar to sanitary materials include pet sheets and pet diapers, and in the present invention, these animal urine treatment products are also included in the sanitary materials.
[0028] The recovered water-absorbent resin is not limited to an embodiment in which the total amount (100% by mass) is the water-absorbent resin alone, and may be a water-absorbent resin composition containing a fibrous substance, a nonwoven fabric, an adhesive, an additive, etc. In addition, when the recovered water-absorbent resin is a water-absorbent resin contained in a used absorbent article, the recovered water-absorbent resin may be in a state of a hydrous gel in which water such as urine water has been taken in. Therefore, the water-absorbent resin may contain a water-absorbent resin in a state of a hydrous gel.
[0029] The mass of the absorbent resin and the recovered absorbent resin is a value converted into solid content unless otherwise specified. For example, when the mass of the absorbent resin contained in the used paper diaper is unknown, the mass of the absorbent resin contained in the unused paper diaper and the general value of the water absorption ratio of the absorbent resin in the used paper diaper are used for calculation, or the content of the absorbent resin (solid content equivalent value) relative to the total mass of the used paper diaper is assumed to be 3% by mass or more and 9% by mass or less, and the mass of the absorbent resin is measured. Although the actual content of the absorbent resin may vary greatly depending on the usage state of the used paper diaper, a person skilled in the art can adjust the decomposition conditions appropriately while checking the actual decomposition state.
[0030] [1-4] Absorbent articles An "absorbent article" is an article used for absorbing water. More specifically, an "absorbent article" is an absorbent article comprising an absorbent body containing a water-absorbent resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is suitably manufactured by blending a water-absorbent resin with a fibrous material, or by sandwiching a water-absorbent resin between fibrous materials and molding the mixture into a film, a tube, a sheet, or the like. Examples of the fibrous material include hydrophilic fibers such as ground wood pulp, cotton linters, crosslinked cellulose fibers, rayon, cotton, wool, acetate, vinylon, and the like.
[0031] The term "absorbent article" includes both unused absorbent articles and used absorbent articles. Here, "used absorbent articles" particularly include used sanitary materials that have absorbed body fluids (absorbed liquids) such as urine and blood. Examples of the sanitary materials include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets.
[0032] [1-5] EDANA, WSP, and NWSP "EDANA" is an abbreviation for European Disposables and Nonwovens Associations, and "WSP" is an abbreviation for World Strategic Partners. EDANA WSP is a European and American standard (almost a global standard) for measuring the physical properties of water-absorbent resins. In the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original EDANA WSP (revised in 2010 / publicly known document).
[0033] "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015."
[0034] [1-5-1] CRC In this specification, the absorbency without load (CRC) is a value measured according to the following method.
[0035] (Measurement of Absorption Capacity under No Load (CRC)) The "CRC" of a water-absorbent resin or a water-absorbent resin composition is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water-absorbent resin or a water-absorbent resin composition for 30 minutes under no pressure in a 0.90 mass % aqueous sodium chloride solution.
[0036] 0.200 g of the water-absorbent resin or water-absorbent resin composition is uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Kogyo Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed, and then immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag is pulled out and drained for 3 minutes using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122) at a centrifugal force (250 G) described in Edana ABSORBENCY II 441.1-99, and then the mass W1 (g) of the bag is measured. In addition, the same operation is performed without using the water-absorbent resin or water-absorbent resin composition, and the mass W0 (g) at that time is measured. Then, from these W1 and W0, the CRC (centrifuge retention capacity) is calculated according to the following formula (1). Formula (1): CRC(g / g)=(W1-W0) / (mass of water-absorbent resin or water-absorbent resin composition)-1
[0037] [1-5-2] Water soluble matter (16-hour value) In this specification, the water-soluble content (16-hour value) is a value measured according to the following method. In this specification, the "water-soluble content (16-hour value)" is also referred to simply as "water-soluble content" or "water-soluble content" or "soluble polymer content".
[0038] (Measurement of water soluble matter (16-hour value)) 184.3g of 0.90% by mass sodium chloride aqueous solution is weighed out into a 250ml plastic container with a lid, 1.00g of water-absorbent resin or water-absorbent resin composition is added to the aqueous solution, and the mixture is stirred for 16 hours to extract the water-soluble components in the resin. After stirring, the extract is filtered using a sheet of filter paper (ADVANTEC Toyo Co., Ltd., product name: (JIS P 3801, No.2), thickness 0.26mm, retention particle size 5μm), and 50.0g of the obtained filtrate is used as the measurement liquid.
[0039] Next, the measurement solution is titrated with a 0.1N-NaOH aqueous solution until the pH becomes 10, and then titrated with a 0.1N-HCl aqueous solution until the pH becomes 2.7. The titration amounts at this time are calculated as [NaOH] ml and [HCl] ml, respectively.
[0040] In addition, the same operation is carried out using only 184.3 g of 0.90 mass % sodium chloride aqueous solution without adding the water-absorbent resin or the water-absorbent resin composition, and the blank titration amount ([bNaOH] ml, [bHCl] ml) is determined.
[0041] When the water absorbent resin or the water absorbent resin composition is composed of a known amount of acrylic acid and a salt thereof, based on the average molecular weight of the monomer and the titration amount obtained by the above operation, the water-soluble content (unit: mass%) in the water absorbent resin or the water absorbent resin composition can be calculated by the following formula (2). Formula (2): Water soluble content (mass%) = 0.1 x (average molecular weight of monomer) x 184.3 x 100 x ([HCl]-[bHCl]) / 1000 / 1.0 / 50.0
[0042] [1-5-3] AAP0.3 (absorption capacity under pressure) "AAP" of the water absorbent resin or water absorbent resin composition of the present invention is an abbreviation for "Absorption Against Pressure" and indicates the absorption capacity against pressure (unit: g / g) for a 0.90 mass% sodium chloride aqueous solution. In this specification, unless otherwise specified, "AAP0.3", "absorption capacity against pressure", and "AAP" are treated as synonyms.
[0043] AAP0.3 is measured in accordance with NWSP 242.0.R2(15) except that the pressure condition is changed from 0.7 psi to 0.3 psi. Specifically, a large excess of 0.9 mass% sodium chloride aqueous solution is used, and 0.9 g of the water absorbent resin or water absorbent resin composition is subjected to pressure of 2.07 kPa (21 g / cm) for 1 hour. 2 After swelling under a pressure of 0.3 psi (0.02 psi), the AAP (absorbency under pressure) is measured. "NWSP" stands for "Non-Woven Standard Procedures-Edition 2015."
[0044] [1-5-4] Residual monomer amount 1.0 g of the water-absorbing resin or water-absorbing resin composition is added to 200 ml of a 0.9% by mass aqueous sodium chloride solution, and stirred at 500 rpm for 1 hour using a 35 mm stirrer tip. The amount of monomer dissolved by this operation (unit: mass ppm) is measured using HPLC (high performance liquid chromatography).
[0045] [1-5-5] Deionized water CRC In the measurement method of [1-5-1] CRC, i) the amount of the water absorbent resin or the water absorbent resin composition used is changed from 0.200 g to 0.020 g, and ii) a 0.9 mass % aqueous sodium chloride solution (physiological saline (abbreviated as saline)) is changed to deionized water, respectively, and the deionized water CRC of the water absorbent resin or the water absorbent resin composition is measured by performing the same operation.
[0046] [1-5-6] Molecular weight of water-soluble portion of water-absorbent resin or water-absorbent resin composition The molecular weight of the water-soluble portion of the water-absorbent resin or the water-absorbent resin composition is measured according to the following procedure.
[0047] (Preparation of measurement samples) The sample is dissolved in the following solvent to obtain a solution with a concentration of 0.1% by mass. The resulting solution is then passed through a filter (GL Sciences: GL Chromatodisk, aqueous 25A, pore size 0.2 μm) to obtain the measurement sample. Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM disodium hydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35 to 6.38). Using this measurement sample, perform GPC measurement under the following measurement conditions.
[0048] (GPC measurement conditions) The sample was subjected to GPC measurement using Viscotec TDAmax manufactured by Malvern Instruments. The measurement device is equipped with a size exclusion chromatograph, a refractive index detector, a light scattering detector and a capillary viscometer. The measurement device and measurement conditions are as follows. Pump and autosampler: Viscotec GPCmax (Malvern Instruments) Guard column: OHpak SB-G (Showa Denko Co., Ltd.) Column: Two OHpak SB-806MHQ (Showa Denko K.K.) columns connected in series Detector: Viscotec TDAmax (Malvern) Solvent: Aqueous solution containing 60 mM sodium dihydrogen phosphate dihydrate, 20 mM sodium dihydrogen phosphate dodecahydrate, and 400 ppm sodium azide (pH 6.35 to 6.38). Flow rate: 0.5mL / min Injection volume: 100μL.
[0049] The water used in GPC measurement should be pure water from which impurities have been thoroughly removed. In addition, GPC measurement should be performed with a sufficient amount of solvent flowing through the measurement device, with the baseline of the detection value stable, and in particular, with no noise peaks in the light scattering detector.
[0050] The measurement device is calibrated using polyoxyethylene glycol [weight average molecular weight (Mw): 21966, molecular weight distribution (Mw / Mn): 1.0, differential refractive index (dn / dc): 0.132, solvent refractive index: 1.33] as a standard sample. The measurement is performed with the differential refractive index (dn / dc) of the measurement target set to 0.12 and the solvent refractive index set to 1.33. Data collection and analysis of the refractive index, light scattering intensity, and viscosity are performed using Viscotek OmniSEC4.7.0 (registered trademark) software.
[0051] After the measurement, the weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mw / Mn) are calculated using the data obtained from the refractive index (RI) and light scattering intensity (angle: 7°) (LALS), as well as the viscometer (DP).
[0052] [1-5-7] Fibrous materials The term "fibrous material" refers to a material having a shape that is at least twice, preferably at least 5 times, more preferably at least 10 times, and even more preferably at least 20 times longer than its thickness (width). Due to the characteristics of this shape, it often has a feature that the specific surface area is larger than that of a particulate material having the same mass. The fibrous material used in one embodiment of the present invention may be either hydrophilic or hydrophobic, and may be either a natural product or a synthetic polymer.
[0053] [2] A method for producing a recycled water-absorbent resin according to one embodiment of the first aspect In one embodiment of the present invention, the method for producing a regenerated water absorbent resin of the present invention comprises treating a raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salts, lithium salts, magnesium salts, calcium salts and iron salts of a carboxyl group with an acidic substance (acid treatment step); and adding a substance containing at least one element selected from the group consisting of potassium element and nitrogen element to the raw water absorbent resin treated with the acidic substance in an amount such that the substitution rate of the carboxyl groups is more than 5 mol % and less than 40 mol %, thereby substituting the carboxyl groups present in the raw water absorbent resin with the element (substitution step).
[0054] [2-1] Pretreatment process Before the raw water absorbent resin is treated with an acidic substance, other treatments such as a washing / sterilization step, a crushing step, a separation step and a dehydration step may be performed (pretreatment step). The raw water absorbent resin is preferably a salt of sodium, potassium, lithium, magnesium, calcium and / or carboxyl groups. and iron salts. The raw water absorbent resin may be a recovered water absorbent resin recovered from used absorbent articles or from waste materials during the water absorbent resin manufacturing process. In addition, when the raw water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles, the raw water absorbent resin may be a water absorbent resin previously separated from the used absorbent articles, or may be a water absorbent resin that is still contained in the used absorbent articles.
[0055] In particular, when the raw material water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles, it is preferable to carry out at least one of a cleaning / sterilization step, a crushing step, a separation step, and a dehydration step, and it is more preferable to carry out at least a dehydration step, and it is particularly preferable to carry out a cleaning / sterilization step, a crushing step, a separation step, and a dehydration step.
[0056] In the case where the raw absorbent resin is a recovered absorbent resin recovered from a used absorbent article, it is preferable to carry out a washing / sterilization step as a pretreatment step. The used absorbent article may be washed and / or sterilized before the acid treatment step, or before the dehydration step (if a dehydration step is carried out), or before the crushing step (if a crushing step is carried out). The washing and / or sterilization may be carried out by placing the used absorbent article in a high-temperature and high-pressure environment, or by using a chemical agent to kill harmful bacteria contained in the used absorbent article. In the case where a chemical agent is used, the chemical agent is not particularly limited as long as the desired cleanliness can be obtained. Examples of the chemical agent include an aqueous solution in which a disinfectant such as sodium hypochlorite and chlorine dioxide is dissolved, ozone water, and electrolyzed water (acidic electrolyzed water). Here, when washing and / or sterilization is carried out using the chemical agent, a solution (dispersion) containing the absorbent resin and the chemical agent can be obtained. In particular, when the washing and / or sterilization is carried out using ozone water, it is preferable to carry out the washing and / or sterilization under acidic conditions. Furthermore, in the above-mentioned cleaning and / or sterilization, it is preferable to carry out the cleaning and / or sterilization in a tank having an agitating blade and / or to circulate the solution to efficiently mix the absorbent article with the drug. After the above-mentioned cleaning and / or sterilization, the cleaned and / or sterilized absorbent article is separated from the liquid by a known method such as a filtration operation. The separated absorbent article can be subjected to an acid treatment step, a dehydration step (if a dehydration step is performed), or a crushing step (if a crushing step is performed).
[0057] When a crushing step is performed as a pretreatment step, the crushing step is a step of crushing the used absorbent articles or the recovered water absorbent resin. The crushing step is performed by physical forces such as stirring, cutting, shredding, and crushing. The crushing step may be performed in a state where the used absorbent articles or the recovered water absorbent resin are immersed in water (aqueous solution). In addition, in order to facilitate separation of the water absorbent resin in the separation step described below, the crushing step may be performed while stirring the used absorbent articles or the recovered water absorbent resin.
[0058] In the case where a separation step is performed as a pretreatment step, the separation step is a step of separating the crushed used absorbent articles or the recovered water-absorbent resin into each component material including the water-absorbent resin and recovering at least the water-absorbent resin. In addition, in the separation step, each component material other than the water-absorbent resin may be recovered. Note that the water-absorbent resin recovered in the separation step may be a water-absorbent resin in a hydrous gel state.
[0059] The method for separating each of the aforementioned constituent materials is not particularly limited, and examples thereof include a method for separating and recovering each of the constituent materials using a screen, and a method for separating and recovering each of the constituent materials from the crushed absorbent article or recovered water-absorbent resin in a state dispersed in water by utilizing the difference in specific gravity of each of the constituent materials. In addition, for example, it is also possible to crush the absorbent article or recovered water-absorbent resin in water in the crushing step to prepare the crushed absorbent article or recovered water-absorbent resin in a state dispersed in water, and to carry out the separation step at the same time.
[0060] When the raw water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles, it is preferable to carry out a dehydration step as a pretreatment step, and more preferably to carry out the dehydration step before carrying out the acid treatment, which can significantly reduce the amount of water-soluble matter (16-hour value) and the amount of residual monomers.
[0061] In one embodiment of the present invention, the raw water absorbent resin is a recovered water absorbent resin recovered from a used absorbent article, which contains a polymer having a sodium salt and / or a lithium salt of a carboxyl group, and the raw water absorbent resin is dehydrated (dehydration step), and then treated with the acidic substance (acid treatment step).
[0062] Here, the "dehydration step" refers to reducing the water content of the swollen water absorbent resin. Specific examples of the method include, but are not limited to, a method of treating the water absorbent resin with a polyvalent metal salt, a method of adding the swollen water absorbent resin gel to a water-soluble hydrophilic organic solvent to dehydrate it, a method of shrinking the gel and releasing the absorbed liquid by changing the pH or temperature in the case of a water absorbent resin whose swelling state changes depending on the pH or temperature change, a method of reducing the water content of the swollen water absorbent resin gel by heating and drying, a method of contacting the water absorbent resin gel with a gas such as heated steam, a method of reducing the water content of the water absorbent resin gel by freeze-drying, and a method of contacting the water absorbent resin gel with another water absorbing agent to have the other water absorbing agent absorb the absorbed liquid in the water absorbent resin. Among these, from the viewpoints of further efficiently reducing the water content, simplicity and effectiveness, the method of treating a water absorbent resin with a polyvalent metal salt, the method of adding to a hydrophilic organic solvent for dehydration, and the method of changing the swelling state by changing pH or temperature are preferred, and the method of treating a water absorbent resin with a polyvalent metal salt and the method of adding to a hydrophilic organic solvent for dehydration are more preferred.
[0063] When the raw water absorbent resin is treated with a polyvalent metal salt, the treatment can be carried out by adding the polyvalent metal salt to the water absorbent resin. For example, a method of contacting the raw water absorbent resin with a solution containing a polyvalent metal salt can be used. More specifically, a method of immersing the raw water absorbent resin in a solution containing a polyvalent metal salt can be used. In this case, the contact (immersion) may be carried out under stirring.
[0064] As the polyvalent metal salt, an alkaline earth metal salt, a transition metal salt, etc. can be used. As the alkaline earth metal salt, a water-soluble salt such as beryllium, magnesium, calcium, strontium, barium, etc. can be used. As the preferred alkaline earth metal salt, calcium chloride, calcium nitrate, magnesium chloride, magnesium nitrate, etc. can be mentioned, with calcium chloride being more preferred. As the transition metal salt, a water-soluble salt such as iron, cobalt, nickel, copper, etc. can be mentioned. As the transition metal salt, any inorganic acid salt, organic acid salt, complex, etc. can be used as long as it is incorporated into the raw water absorbent resin. Among them, from the viewpoint of cost, availability, etc., the transition metal salt is preferably an inorganic acid salt or an organic acid salt. As the inorganic acid salt, for example, iron salts such as iron chloride, iron sulfate, iron phosphate, iron nitrate, etc.; cobalt salts such as cobalt chloride, cobalt sulfate, cobalt phosphate, cobalt nitrate, etc.; nickel salts such as nickel chloride, nickel sulfate, etc.; copper salts such as copper chloride, copper sulfate, etc. can be mentioned. Examples of the organic acid salts include iron lactate, cobalt acetate, cobalt stearate, nickel acetate, and copper acetate. The polyvalent metal salts may be used alone or in combination of two or more. Among these, the polyvalent metal salt is preferably an alkaline earth metal salt, more preferably at least one selected from the group consisting of calcium chloride, calcium nitrate, magnesium chloride, and magnesium nitrate, and particularly preferably calcium chloride.
[0065] When the raw water absorbent resin is brought into contact with a solution containing a polyvalent metal salt, the solvent that can be used is not particularly limited as long as it can dissolve the polyvalent metal salt, and can be appropriately selected depending on the type of the polyvalent metal salt. Specifically, water, lower alcohols such as methanol and ethanol, acetonitrile, etc., Examples of suitable polyvalent metal salts include ketones such as ketones, methyl ethyl ketone, etc. The concentration of the polyvalent metal salt in the solution is not particularly limited. The concentration of the polyvalent metal salt in the solution is, for example, 0.5% by mass or more and 10.0% by mass or less, and preferably 1.0% by mass or more and 5.0% by mass or less.
[0066] The amount of polyvalent metal salt used may be determined based on the state of shrinkage of the water absorbent resin after the dehydration operation, i.e., after treatment with the polyvalent metal salt. For example, the mixed amount (addition amount) of the polyvalent metal salt is preferably 50 parts by mass or more and 100 parts by mass or less, more preferably 60 parts by mass or more and 90 parts by mass or less, relative to 100 parts by mass of the raw water absorbent resin (solid content). With such an amount, the raw water absorbent resin can be sufficiently dehydrated.
[0067] The conditions for the dehydration treatment using the polyvalent metal salt are not particularly limited as long as the conditions are sufficient for the polyvalent metal ion to be incorporated into the raw water absorbent resin. The dehydration treatment time is preferably 5 minutes or more and 3 hours or less, more preferably 5 minutes or more and 2 hours or less, and even more preferably 10 minutes or more and 1 hour or less. The dehydration treatment temperature is preferably 5°C or more and 80°C or less, more preferably 10°C or more and 70°C or less, and even more preferably 15°C or more and 60°C or less. Under such conditions, the raw water absorbent resin can be sufficiently dehydrated.
[0068] The dehydration treatment may be carried out once or repeatedly until a desired shrinkage state is obtained.
[0069] [2-2] Acid treatment process If necessary, after the pretreatment in the above [2-1], the raw water absorbent resin is treated with an acidic substance (acid treatment step). By this step, the salt of the carboxyl group (-COOX or -COO-Y-OOC-; X is sodium, potassium or lithium, and Y is an alkaline earth metal or a transition metal (e.g., magnesium, calcium, iron, etc.)) in the raw water absorbent resin is converted to a carboxyl group (-COOH).
[0070] The acid treatment method is not particularly limited as long as it can bring the raw water absorbent resin into contact with an acidic substance. For example, a method of mixing the raw water absorbent resin with an acidic substance, adding an acidic substance to the raw water absorbent resin, adding the raw water absorbent resin to an acidic substance, immersing the raw water absorbent resin in a solution containing an acidic substance, etc. can be used.
[0071] The acidic substance is not particularly limited, and for example, inorganic acids and / or organic acids can be used. Examples of inorganic acids include sulfuric acid, hydrochloric acid, and nitric acid. Examples of the organic acid include organic substances having an acid group, such as a carboxyl group, a sulfo group, and the like. The acidic substance may be one selected from the inorganic acids and organic acids described above, or a mixture of two or more selected acidic substances. The acidic substance may be a combination of an inorganic acid and an organic acid. Specific examples of the organic acid include citric acid, tartaric acid, malic acid, succinic acid, oxalic acid, gluconic acid, pentanoic acid, butanoic acid, propionic acid, glycolic acid, acetic acid, formic acid, and sulfonic acid. Examples of the sulfonic acid include methanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, and p-toluenesulfonic acid. Among these, hydrochloric acid, citric acid, and sulfuric acid are preferred, and hydrochloric acid and citric acid are more preferred. The acid treatment process can also serve as a dehydration process. Therefore, when the acid treatment step is carried out, the dehydration step can be omitted.
[0072] When the acidic substance is used in the form of a solution, the solvent that can be used may be any solvent capable of dissolving the acidic substance, and examples of such solvents include water, lower alcohols such as methanol and ethanol, and ketones such as acetone and methyl ethyl ketone. The above-mentioned solvents may be used alone or in combination of two or more kinds. The concentration of the acidic substance in the solution is not particularly limited, but for example, For example, it is from 0.5% by mass to 20% by mass, and preferably from 1% by mass to 10% by mass.
[0073] The amount of the acidic substance to be added may be an amount that can sufficiently convert the salt of the carboxyl group in the raw water absorbent resin to a carboxyl group (-COOH). For this reason, the amount of the acidic substance to be added is preferably in excess of the salt of the carboxyl group in the raw water absorbent resin. The amount of the acidic substance to be added is, for example, more than 1.0 mole and not more than 7.0 moles, preferably 1.1 moles or more and not more than 5.0 moles, more preferably 1.2 moles or more and not more than 4.0 moles, and even more preferably 1.2 moles or more and not more than 3.5 moles, as the acid group of the acidic substance (such as a carboxyl group or a sulfo group) per mole of the salt of the carboxyl group in the raw water absorbent resin. Note that, when the number (molar number) of the salt of the carboxyl group (-COOX or -COO-Y-OOC-; X is sodium or lithium, and Y is an alkaline earth metal or a transition metal (e.g., magnesium, calcium, iron, etc.)) in the raw water absorbent resin is unknown, an amount exceeding the above-mentioned amount may be added. Alternatively, for example, the amount of the acidic substance to be added can be determined by neutralization titration.
[0074] The acid treatment conditions are appropriately selected in consideration of the conditions under which the salt of the carboxyl group in the raw water absorbent resin can be sufficiently converted to a carboxyl group (-COOH). For example, the acid treatment temperature is preferably 5°C or more and 100°C or less, more preferably 10°C or more and 90°C or less, and even more preferably 15°C or more and 80°C or less. The acid treatment time is preferably 1 minute or more and 2 hours or less, more preferably 5 minutes or more and 60 minutes or less, and even more preferably 10 minutes or more and 30 minutes or less. When the acid treatment is performed by mixing the raw water absorbent resin with a solution containing an acidic substance, the acid treatment may be performed under stirring.
[0075] The acid treatment may be carried out once or repeatedly until all the salts of the carboxyl groups are converted into carboxyl groups.
[0076] The raw water absorbent resin treated with the acidic substance may remain in the dispersion liquid after the acid treatment (i.e., in the state of the acid treatment liquid). Alternatively, the raw water absorbent resin treated with the acidic substance may be in a state in which it is taken out from the dispersion liquid after the acid treatment. Here, the operation for taking out the raw water absorbent resin from the acid treatment liquid is not particularly limited, and for example, a known method such as a filtration operation can be used. In one example, the dispersion liquid after the acid treatment is filtered through a wire mesh of 50 mesh or more and 200 mesh or less (e.g., 100 mesh), and if necessary, is left as it is.
[0077] [2-3] Cleaning process The acid-treated raw water absorbent resin may be washed. In one embodiment of the present invention, the acid-treated raw water absorbent resin is washed with water to obtain a raw water absorbent resin washed with water. This process can remove or reduce the content of impurities (e.g., acidic substances, polyvalent metal ions) present on the surface, inside, or in gaps between particles of the acid-treated raw water absorbent resin, thereby improving the water absorption performance (e.g., deionized water CRC) of the final product, the regenerated water absorbent resin.
[0078] When the washing step is carried out, the washing operation is not particularly limited, and a known method can be used. For example, a method of immersing the acid-treated raw water absorbent resin in a washing liquid and stirring it, a method of spraying or showering the washing liquid onto the acid-treated raw water absorbent resin, etc. can be mentioned. The washing operation may be repeated. By repeating the washing operation, the washing effect is enhanced, and a larger amount of impurities (e.g., acidic substances, polyvalent metal ions) can be removed or the content thereof can be reduced.
[0079] The washing liquid used in the washing step may be water, saline, or seawater, and preferably water. The type of water (washing water) may be deionized water, tap water, or distilled water. etc. can be used.
[0080] The washing conditions when performing the washing step are not particularly limited. For example, the washing temperature (liquid temperature of the washing liquid) is from room temperature to the boiling point of the washing liquid. Alternatively, high-temperature steam may be used. The washing temperature is preferably from 5°C to 100°C, more preferably from 10°C to 90°C, and even more preferably from 15°C to 80°C. When high-temperature washing water or high-temperature steam is used in the washing operation, not only the washing effect but also the sterilization effect can be expected. The washing time is, for example, from 1 minute to 60 minutes, and preferably from 5 minutes to 30 minutes.
[0081] The raw water absorbent resin after the washing treatment may remain in the washing liquid. Alternatively, the raw water absorbent resin after the washing treatment may be in a state of being taken out from the washing liquid after the washing treatment is completed. Here, the operation of taking out the raw water absorbent resin from the washing liquid is not particularly limited, and for example, a known method such as a filtration operation can be used. In one example, the dispersion after the washing treatment is completed is filtered through a wire mesh of 50 mesh or more and 200 mesh or less (for example, 100 mesh), and if necessary, is left as it is.
[0082] [2-4] Substitution process (neutralization process) In this step, a substance containing at least one element selected from the group consisting of potassium and nitrogen elements (K / N-containing substance) is added to the raw water absorbent resin treated in the acid treatment step [2-2] or the washing step [2-3] in such an amount that the substitution rate of the carboxyl groups is more than 5 mol % and less than 40 mol %. As a result, hydrogen atoms of carboxyl groups (-COOH) in a ratio of more than 5 mol % and less than 40 mol % of all carboxyl groups present in the raw water absorbent resin (raw polymer) after the acid treatment are substituted (neutralized) with potassium elements (-COOK) or nitrogen elements. Regarding nitrogen elements, from the viewpoints that carboxyl groups are easily substituted and that the recycled water absorbent resin is easily utilized by plants when used as a water retention material for plant growth, etc., it is preferable to use a nitrogen-containing substance in which the carboxyl groups (-COOH) are substituted with ammonium ions (-COO - NH4 + ) is preferably converted (substituted).
[0083] Here, the amount of K / N-containing substance added is an amount such that the substitution rate of the carboxyl group is more than 5 mol% and less than 40 mol%. When the amount of K / N-containing substance added is such that the substitution rate is 5 mol% or less, the regenerated water-absorbent resin obtained is inferior in water absorption ability. Therefore, the regenerated water-absorbent resin obtained is not suitable as a water-retaining material or a water-absorbent article. In addition, the regenerated water-absorbent resin does not have sufficient amounts of potassium element and nitrogen element. Therefore, the potassium source or nitrogen source is not sufficiently supplied to the plant, so that even if the regenerated water-absorbent resin is used alone, the plant growth (particularly the germination rate) is not fully exhibited. On the other hand, when the amount of K / N-containing substance added is such that the substitution rate is 40 mol% or more, the plant growth (particularly the germination rate) is reduced, although the reason is unclear. Therefore, the regenerated water-absorbent resin obtained is not suitable as a water-retaining material for plant growth. In particular, from the viewpoint of usefulness as a water retention material for plant growth (particularly further improvement of germination rate), the substitution rate of carboxyl groups is preferably 10 mol% to 39 mol%, more preferably 15 mol% to 35 mol%, and particularly preferably 15 mol% to 30 mol%. With such a substitution rate, plant growth (particularly germination rate) can be further improved while maintaining a moderate water retention capacity (e.g., deionized water CRC).
[0084] The replacement (neutralization) is carried out by contacting the raw water absorbent resin treated in the acid treatment step [2-2] or the washing step [2-3] with a predetermined amount of K / N-containing substance. For example, a method of mixing the raw water absorbent resin with the K / N-containing substance, adding a K / N-containing substance or a solution containing a K / N-containing substance to the raw water absorbent resin, immersing the raw water absorbent resin in a solution containing a K / N-containing substance, etc. can be used. Among these, a method of adding a K / N-containing substance or a solution containing a K / N-containing substance to the raw water absorbent resin is preferred, and a method of adding and mixing a K / N-containing substance or a solution containing a K / N-containing substance to the raw water absorbent resin is more preferred. In the method of adding a K / N-containing substance or a solution containing a K / N-containing substance to the raw water absorbent resin, the addition method may be carried out stepwise or continuously. In addition, as the addition method, an addition method such as lump addition, dropwise addition, or divided addition is preferably used.
[0085] The amount of the K / N-containing substance to be added is an amount that will result in the substitution rate of the carboxyl group. In addition, when the number of carboxyl groups (-COOH) in the raw water absorbent resin after the treatment in the acid treatment step [2-2] or the washing step [2-3] is unknown, the amount of the K / N-containing substance to be added can be determined, for example, by neutralization titration of the water absorbent resin.
[0086] Examples of K / N-containing substances include potassium-containing substances such as potassium hydroxide, potassium sulfate, potassium chloride, potassium carbonate, potassium hydrogen carbonate, potassium nitrate, and potassium chloride; and nitrogen-containing substances such as ammonium carbonate, ammonium chloride, ammonium nitrate, ammonium sulfate, and diammonium hydrogen phosphate. Among these, potassium hydroxide, ammonium carbonate, and potassium carbonate are preferred, and potassium hydroxide and potassium carbonate are particularly preferred, from the viewpoints that the carboxyl group is easily substituted and that the regenerated water absorbent resin is easily utilized by plants when used as a water retention material for plant growth.
[0087] In addition, when the K / N-containing substance is used in the form of a solution, the solvent that can be used may be any solvent capable of dissolving the K / N-containing substance, such as water, lower alcohols such as methanol and ethanol, and ketones such as acetone and methyl ethyl ketone. The solvents may be used alone or in combination of two or more. The concentration of the K / N-containing substance in the solution is not particularly limited, but is, for example, 5% by mass or more and 60% by mass or less, and preferably 10% by mass or more and 50% by mass or less. When the K / N-containing substance is directly added to the raw water absorbent resin, the form of the K / N-containing substance is not particularly limited, and may be powdery, granular, or the like.
[0088] The substitution treatment conditions are appropriately selected in consideration of the conditions under which the carboxyl groups in the raw water absorbent resin can be substituted at a predetermined substitution rate. For example, the substitution treatment temperature is preferably 5°C or more and 100°C or less, more preferably 10°C or more and 90°C or less, and even more preferably 15°C or more and 80°C or less. The substitution treatment time is preferably 5 minutes or more and 2 hours or less, more preferably 10 minutes or more and 150 minutes or less, and even more preferably 20 minutes or more and 60 minutes or less. The raw water absorbent resin and the K / N-containing substance may be mixed under stirring.
[0089] The replacement process may be carried out once or repeatedly until a predetermined replacement rate is obtained.
[0090] [2-5] Other processes In addition to the above-mentioned steps, the production method according to the present invention may further include a drying step, a pulverizing step, a classification step, a surface cross-linking step, a sizing step, and the like, as necessary.
[0091] [2-5-1] Drying process This step is a step of obtaining a dried polymer by drying the regenerated water-absorbent resin to a desired resin solid content. The resin solid content is determined from the loss on drying (the change in mass when 1 g of the water-absorbent resin is heated at 180° C. for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass. The drying method is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, and high humidity drying using high-temperature water vapor. The drying temperature (the temperature of the hot air in the case of hot air drying) is, for example, about 20° C. to 250° C. In addition, other factors such as the wind speed of the hot air and the drying time may be selected in addition to the drying temperature. The drying conditions may be appropriately set depending on the moisture content and total mass of the water absorbent resin to be dried and the intended resin solid content. When band drying is performed, the conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.
[0092] [2-5-2] Crushing process This step is a step of pulverizing (and classifying, if necessary) the regenerated water-absorbent resin or the dried product obtained in the above drying step.
[0093] The pulverizer (disintegrator) is not particularly limited, and examples thereof include a vibration mill, a roll granulator, a knuckle type pulverizer, a roll mill, a high-speed rotary pulverizer (a pin mill, a hammer mill, a screw mill), a cylindrical mixer, etc. From the viewpoint of causing less damage to the dried material, a roll granulator (Matsubo Corporation), a granulator (Kurimoto Iron Works, Ltd.), a Randle mill (Tokuju Machine Works, Ltd.), etc. can be used.
[0094] [2-5-3] Classification process A classification step may be performed after the pulverization. In this case, the classification step is a step of removing coarse particles and fine powder from the pulverized product obtained above using a classifier. As the classifier, a vibrating or rocking type sieve classifier using a sieve net is used.
[0095] [2-5-4] Surface crosslinking step This step is a step of providing a portion with a higher crosslink density on the surface layer (particularly, a portion several tens of μm from the surface of the water-absorbent resin precursor) of the regenerated water-absorbent resin or the water-absorbent resin obtained through any of the above steps (hereinafter, also simply referred to as "water-absorbent resin precursor"), and may be composed of a mixing step, a heat treatment step, and a cooling step (optional). In the surface crosslinking step, a surface-crosslinked water-absorbent resin is obtained by radical crosslinking, surface polymerization, crosslinking reaction with a surface crosslinking agent, etc. on the surface of the water-absorbent resin precursor.
[0096] (Surface cross-linking agent) The surface cross-linking agent used in one embodiment of the present invention is not particularly limited, but includes organic or inorganic surface cross-linking agents. Among them, from the viewpoint of the physical properties of the water-absorbent resin, the handling property of the surface cross-linking agent, etc., organic surface cross-linking agents that react with carboxyl groups are preferred. For example, one or more surface cross-linking agents disclosed in U.S. Patent No. 7,183,456 can be mentioned. More specifically, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyvalent amine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal compounds, alkylene carbonate compounds, cyclic urea compounds, etc. can be mentioned.
[0097] Specifically, ethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, 1,3-propanediol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, polypropylene glycol, glycerin, polyglycerin, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,2-cyclohexanol, trimethylolpropane, polyhydric alcohol compounds such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol polyglycidyl ether, glycidol, sorbitol polyglycidyl ether, pentaerythritol, diethanolamine, triethanolamine, polyoxypropylene, oxyethylene-oxypropylene block copolymer, pentaerythritol, sorbitol, etc.; Epoxy compounds such as taerythritol polyglycidyl ether, trimethylolpropane polyglycidyl ether, neopentyl glycol diglycidyl ether, and 1,6-hexanediol diglycidyl ether; polyamine compounds and their inorganic or organic salts such as ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, and polyethyleneimine; polyisocyanate compounds such as 2,4-tolylene diisocyanate and hexamethylene diisocyanate; aziridine compounds such as polyaziridine; polyoxazoline compounds such as 1,2-ethylenebisoxazoline, bisoxazoline, and polyoxazoline; carbonic acid derivatives such as urea, thiourea, guanidine, dicyandiamide, and 2-oxazolidinone; 1,3-dioxolan-2-one (ethylene carbonate), 4-methyl-1,3 -dioxolan-2-one, 4,5-dimethyl-1,3-dioxolan-2-one, 4,4-dimethyl-1,3-dioxolan-2-one, 4-ethyl-1,3-dioxolan-2-one, 4-hydroxymethyl-1,3-dioxolan-2-one, 1,3-dioxan-2-one, 4-methyl-1,3-dioxan-2-one, 4,6-dimethyl-1,3-dioxan-2-one, and other alkylene carbonate compounds; epichlorohydrin; Examples of the surface crosslinking agent include haloepoxy compounds such as α-methylepichlorohydrin, epibromohydrin, and α-methylepichlorohydrin, and polyvalent amine adducts thereof; oxetane compounds; silane coupling agents such as γ-glycidoxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane; and polyvalent metal compounds such as hydroxides, chlorides, sulfates, nitrates, or carbonates of zinc, calcium, magnesium, aluminum, iron, zirconium, and the like. Two or more of these may be used in combination. Among the surface crosslinking agents, one or more selected from polyhydric alcohol compounds, polyvalent metal compounds, epoxy compounds, oxazoline compounds, and alkylene carbonate compounds are preferred.
[0098] The amount of the surface crosslinking agent used (when a plurality of agents are used, the total amount used) is preferably 0.01 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. The surface crosslinking agent is preferably added as an aqueous solution, and in this case, the amount of water used is preferably 0.5 to 20 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the water-absorbent resin precursor. Furthermore, when a hydrophilic organic solvent is used as necessary, the amount used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the water-absorbent resin precursor.
[0099] (Mixing process) This step is a step of mixing the water-absorbent resin precursor with the surface crosslinking agent. The method of mixing the surface crosslinking agent is not particularly limited, but for example, a method of preparing a surface crosslinking agent solution in advance and mixing the liquid with the water-absorbent resin precursor is preferred. In this case, the surface crosslinking agent solution is mixed with the water-absorbent resin precursor by more preferably spraying or dropping, and more preferably spraying.
[0100] The device for carrying out the mixing is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.
[0101] (Heat treatment process) This step is a step in which heat is applied to the mixture discharged from the mixing step to cause a crosslinking reaction on the surface of the water-absorbent resin precursor.
[0102] The device for carrying out the crosslinking reaction is not particularly limited, but a paddle dryer is preferable. The reaction temperature in the crosslinking reaction is appropriately set depending on the type of surface crosslinking agent used, and is preferably 50°C or more and 300°C or less, more preferably 100°C or more and 200°C or less. The reaction time in the crosslinking reaction is appropriately set depending on the moisture content of the object of the heat treatment step, the type of surface crosslinking agent, the thermal efficiency of the heating device, and the like, and is preferably continued until the moisture content becomes 10 mass% or less. For example, the reaction time in the crosslinking reaction is, for example, from 10 minutes to 120 minutes, and preferably from 30 minutes to 90 minutes.
[0103] (cooling process) This step is an optional step that is installed as necessary after the heat treatment step. The cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. The water-absorbent resin obtained in the heat treatment step is forcibly cooled, as necessary, to preferably 40°C or more and 80°C or less, more preferably 50°C or more and 70°C or less, in the cooling step.
[0104] After the surface cross-linking step, a sizing step may be further carried out. In addition to the above, the method according to the present invention may include at least one step selected from the steps of adding various additives, removing fine powder, recycling fine powder (recovering fine powder), and filling. Furthermore, various known steps may be included depending on the purpose. The fine powder removed in the removing fine powder step may be used as a recovered water absorbent resin.
[0105] [2-5-5] Particle sizing process This step is a step for adjusting the particle size of the surface-crosslinked water-absorbent resin. This particle size regulation step provides a water-absorbent resin whose particle size or particle size distribution is more actively controlled.
[0106] Preferably, the sizing step includes a crushing step and / or a classification step. The crushing step is a step of adjusting the particle size by crushing the loosely aggregated granular material after the surface cross-linking step with a crusher. The classification step is a step of removing coarse particles and fine powder from the surface cross-linked granular material or the crushed material thereof with a classifier.
[0107] The crusher is not particularly limited, and examples thereof include a vibration mill, a roll granulator, a knuckle type crusher, a roll mill, a high-speed rotary crusher (pin mill, hammer mill, screw mill), a cylindrical mixer, etc. Those that cause little damage to the surface cross-linked water absorbent resin are preferred, and specific examples thereof include a roll granulator (Matsubo Co., Ltd.), a granulator (Kurimoto Iron Works Co., Ltd.), and a Randel Mill (Tokuju Co., Ltd.). As a classifier, a vibrating or rocking type sieve classifier using a sieve net is used. It is also possible to omit the crushing step in this process.
[0108] [3] Properties of recycled water-absorbent resin The regenerated water absorbent resin obtained by the production method according to the present invention has a ratio of more than 5% to less than 40% of the total number of carboxyl groups (the total number of -COOH and -COOZ (Z = K or N-containing groups)) to potassium elements (-COOK) or nitrogen elements (preferably ammonium ions, -COO - NH4 + ) is substituted.
[0109] The recycled water absorbent resin obtained by the production method according to the present invention, when used as a water retention material, preferably satisfies at least one, more preferably at least two, and most preferably all of the following [3-1], [3-2], and [3-3].
[0110] [3-1] Water soluble matter (16-hour value) The regenerated water absorbent resin produced by the method according to the present invention preferably has a small water-soluble content (16-hour value). In one embodiment, the water-soluble content (16-hour value) of the regenerated water absorbent resin produced by the method according to the present invention or the water retention agent containing the water absorbent resin is 20% by mass or less. In one embodiment, the water-soluble content (16-hour value) of the regenerated water absorbent resin or the water retention agent containing the water absorbent resin is less than 20.0% by mass, 19.0% by mass or less, 18.0% by mass or less, less than 17.0% by mass, 16.0% by mass or less, 15.0% by mass or less, 14.0% by mass or less, 13.0% by mass or less, or 12.0% by mass or less (lower limit: 0% by mass). By setting the water-soluble content at such a level, when the regenerated water absorbent resin is used in a sanitary material, the toughness of the polymer structure can be improved, and the process damage resistance and water absorption properties (particularly AAP0.3) can be improved. In addition, when used as a water-retaining material for plant growth, it can further suppress and prevent changes in water absorption properties caused by external environments such as soil.
[0111] [3-2] Residual monomer amount The recycled water absorbent resin produced by the method according to the present invention has a small amount of residual monomer. In one embodiment, the recycled water absorbent resin produced by the method according to the present invention or the water retention agent containing the water absorbent resin has a residual monomer amount of 100 mass ppm or less. In one embodiment, the recycled water absorbent resin or the water retention agent containing the water absorbent resin has a residual monomer amount of 75 mass ppm or less, 50 mass ppm or less, 40 mass ppm or less, 35 mass ppm or less, 30 mass ppm or less, 20 mass ppm or less, less than 15 mass ppm, or 10 mass ppm or less (lower limit: 0 mass ppm). By setting the residual monomer amount in this range, low skin irritation can be expected when the recycled water absorbent resin is used for sanitary materials. In addition, when the recycled water absorbent resin is used as a water retention material for plant growth, a water absorbent resin composition with even greater safety can be provided.
[0112] [3-3] Deionized water CRC (absorption capacity without pressure) The absorbency without pressure (deionized water CRC) of the regenerated water absorbent resin produced by the method according to the present invention is usually 5 g / g or more, preferably 50 g / g or more, more preferably 60 g / g or more, even more preferably more than 70 g / g, and particularly preferably 80 g / g or more. There is no particular limit to the upper limit, and a higher deionized water CRC is preferable, but from the viewpoint of the balance with other physical properties, it is preferably 400 g / g or less, more preferably 350 g / g or less, and even more preferably 320 g / g or less. By setting the absorbency without pressure (deionized water CRC) at such a level, sufficient water retention can be ensured when used as a water retention material for plant growth.
[0113] [4] Method for producing a water-absorbent resin according to one embodiment of the second aspect The above-mentioned method produces a recycled water-absorbent resin. The recycled water-absorbent resin thus obtained can be used as a raw material for a new water-absorbent resin.
[0114] That is, in one embodiment of the second aspect of the present invention, a method for producing a water absorbent resin by using a method according to the present invention and using the regenerated water absorbent resin as a part of a raw material is provided.
[0115] In one aspect of the second embodiment, the method for producing a water absorbent resin is a method for producing a regenerated water absorbent resin in which hydrogen atoms of carboxyl groups present in a raw water absorbent resin (raw polymer skeleton) are substituted with at least one of potassium element and nitrogen element (nitrogen-containing group, preferably ammonium ion) according to the method according to one embodiment of the first aspect, and then using the regenerated water absorbent resin as a part of the raw material to newly produce a water absorbent resin. The "new production of a water absorbent resin" means the production of a conventional water absorbent resin using a monomer constituting the water absorbent resin as a raw material. The process for producing a water-absorbent resin is any one of a process for preparing an aqueous monomer solution, a polymerization process, a hydrogel crushing process, a drying process, and a surface crosslinking process. These processes are not particularly limited and are known. For example, see International Publication No. 2009 / 123197, U.S. Patent Application Publication No. 2008 / 0194863, U.S. Patent Application Publication No. 2005 / 0215734, U.S. Patent No. 7265190, U.S. Patent No. 4893999, U.S. Patent No. 6241928, U.S. Patent Application Publication No. 2005 / 215734, and the like. No. 6,987,151, U.S. Pat. No. 6,710,141, WO 2011 / 126079, WO 2006 / 100300, WO 2011 / 025012, WO 2011 / 025013, WO 2011 / 111657, and the like, or the above methods can be used with appropriate modifications.
[0116] [5] Method for producing a water-retaining material according to one embodiment of the third aspect The regenerated water absorbent resin produced by the above method has a moderate water retention capacity (e.g., deionized water CRC). In addition, the regenerated water absorbent resin produced by the above method has a moderate potassium source or nitrogen source inside the polymer skeleton. Therefore, the regenerated water absorbent resin has excellent plant growth properties (particularly germination rate). In addition, the regenerated water absorbent resin produced by the above method retains the potassium source and nitrogen source inside the polymer skeleton without flowing out even after water absorption or rainfall. Therefore, the regenerated water absorbent resin obtained in this manner is suitably used as a water retention material (particularly a water retention material for plant growth).
[0117] That is, in one aspect of the third embodiment, there is provided a method for producing a water retention material (particularly a water retention material for plant cultivation) which comprises producing a recycled water absorbent resin using the method according to the present invention.
[0118] As described above, the recycled water absorbent resin produced by the method has a suitable water retention capacity (e.g., deionized water CRC) and fertilizer source (potassium source, nitrogen source). Therefore, the recycled water absorbent resin produced by the method according to the present invention can be used as it is as a water retention material (particularly a water retention material for plant cultivation). Alternatively, the recycled water absorbent resin produced by the method according to the present invention can be used as a water retention material in combination with other additives (e.g., soil, leaf mold, phosphorus source).
[0119] That is, in another embodiment of the third aspect, there is provided a water retention material (particularly a water retention material for plant cultivation) that includes or is composed of the recycled water absorbent resin produced using the method of the present invention.
[0120] [6] Recycled water-absorbent resin according to one embodiment of the fourth aspect In one embodiment of the fourth aspect, there is provided a water-absorbent resin recycled from a used absorbent article or a waste from a water-absorbent resin production process, the water-absorbent resin comprising a polymer having a carboxyl group and a part of the carboxyl group being substituted with at least one element selected from the group consisting of a potassium element and a nitrogen element.
[0121] In this embodiment, the polymer is preferably substituted with potassium element at a substitution rate of more than 5 mol% and less than 40 mol% (preferably 10 mol% to 39 mol%, more preferably 15 mol% to 35 mol%, particularly preferably 15 mol% to 30 mol%). The polymer is preferably substituted with nitrogen element at a substitution rate of more than 5 mol% and less than 40 mol%. The polymer preferably has ammonium salt (-COONH4) of carboxyl group at a substitution rate of more than 5 mol% and less than 40 mol%. A polymer having such a substitution rate can further improve plant growth (particularly germination rate) while ensuring a moderate water retention capacity (e.g., deionized water CRC). Therefore, recycled water absorbent resin can be suitably used as a water retention material for plant growth.
[0122] [7] Water-retaining material according to one embodiment of the fifth aspect The recycled water absorbent resin according to one embodiment of the fourth aspect can be suitably used as a water retention material for plant growth.
[0123] In one embodiment of the fifth aspect, there is provided a water retention material comprising or consisting of the recycled water absorbent resin according to the present invention.
[0124] The water retention material according to this embodiment gels when water is supplied (irrigated), and then retains water inside. Therefore, the water retention material according to this embodiment can function as a water supply source for the plant body during the growth of the plant body. The water retention material according to this embodiment supports the nutrient sources of the plant body, such as a potassium source and a nitrogen source, and gradually releases the nutrient sources. Therefore, the water retention material according to this embodiment has excellent germination rate and rooting rate at the time of sowing, and continues to gradually release the nutrient sources for a long period of time, so that it can continue to promote the growth and development of the plant. In addition, the water retention material according to this embodiment can be directly cultivated with the swelling gel. The water retention material according to this embodiment can be expected to improve soil quality and promote greening by applying it to soil or sandy soil. More specifically, the water retention material according to this embodiment can be used as a water retention carrier for rice field cultivation, open-field cultivation, water-saving cultivation, greening method, etc., and can be a water retention carrier for plants that has a high water absorption rate, is easy to handle, and does not inhibit plant growth. The water retention material according to this embodiment can be used as an alternative soil, and can ensure excellent germination and rooting rates without using other plant cultivation carriers in combination. In addition, because the plant can be rooted in the water retention material, the plant can be supported or carried. The water retention material according to this embodiment can be in the form of granules, and in this case, it shows excellent powder fluidity. Therefore, it can be a water retention material for plant cultivation (e.g., hydroculture) that is excellent in workability and handling.
[0125] Therefore, according to the present invention, there is provided a water retaining material for plant cultivation for soil improvement and greening, which has extremely excellent irrigation efficiency.
[0126] The water retention material according to this embodiment may further contain other additives such as deodorants, antibacterial agents, pest and animal repellents, agricultural chemicals (insecticides, fungicides, herbicides, etc.), plant activators, plant life extension agents, plant hormones, minerals, pigments, dyes, thickeners, adhesives, salts, pH adjusters, kaolin soil, clay, soil, etc. The content of the other additives in this case may be appropriately selected depending on the application, and may be, for example, more than 0% by mass and 30% by mass or less, preferably 3% by mass or more and 10% by mass or less, relative to the water retention material.
[0127] The water-retentive material according to this embodiment may be used, for example, by being spread on fields or may be gelled and used as a water-retentive material in a seedbed or the like. Alternatively, the water-retentive material according to this embodiment may be mixed with artificial ground soil for use in dry areas such as deserts and sand dunes, median strips and side strips of roads, roadside trees, indoor ornamental use, rooftop greening of buildings, etc. Alternatively, the water-retentive material according to this embodiment may be included in a formed seedling or the like and transplanted together with a plant. The type and state of the target seeds and plants are not limited, and it can be used, for example, for seed germination, seedling raising, growth of leafy vegetables, fruit vegetables, root vegetables, flowers, etc., and replanting of mature trees.
[0128] [8] Water-absorbing resin composition according to one embodiment of the sixth aspect In one embodiment of the present invention, the water absorbent resin composition of the present invention includes a water absorbent resin having a carboxyl group, and a part of the carboxyl group being substituted with at least one element selected from the group consisting of potassium element and nitrogen element at a substitution rate of 5 mol % or more and 100 mol % or less, and a fibrous material.
[0129] In the above [2], from the viewpoint of plant growth (particularly germination rate), it was necessary to set the substitution rate of the carboxyl group to less than 40 mol%. On the other hand, from the viewpoint of higher water absorption capacity, a higher substitution rate of the carboxyl group is preferable. For this reason, the present inventors have conducted extensive research into measures for improving plant growth (particularly germination rate) even if the substitution rate of the carboxyl group is increased. As a result, they have found that good plant growth can be achieved even if the substitution rate of the carboxyl group is increased by combining with a fibrous material. This is presumably due to the following reasons. Note that the present invention is not limited by the following presumption.
[0130] The water absorbent resin composition according to the present embodiment further contains fibrous material in addition to the (regenerated) water absorbent resin. A water absorbent resin with a high substitution rate (neutralization rate) of carboxyl groups can hold a large amount of water (high water absorption per unit mass), but the water absorption speed is not so fast. A fibrous material has a low water absorption per unit mass compared to a water absorbent resin (about 1 / 10 of the water absorbent resin), but is excellent in short-term water absorption (high water absorption speed). When water is sprayed onto a water absorbent resin composition in which these are combined, the fibrous material quickly captures the sprayed water and transfers the water captured by the fibrous material to the water absorbent resin. Therefore, according to the water absorbent resin composition according to the present embodiment, the fibrous material can capture the sprayed water that could not be captured by the water absorbent resin alone from the viewpoint of water absorption speed, so that the amount of water captured can be made larger than that of the water absorbent resin alone. The presence of water is very important for the growth of plants. Therefore, a water-absorbent resin composition in which a water-absorbent resin is combined with a fibrous material can efficiently capture sprayed water without adversely affecting the water-absorbing properties of the water-absorbent resin, thereby improving plant growth.
[0131] [8-1] Water-absorbing resin In this embodiment, the water-absorbent resin has carboxyl groups, and a part of the carboxyl groups is substituted with at least one element selected from the group consisting of potassium and nitrogen at a substitution rate of 5 mol% to 100 mol%. From the viewpoint of further improving water absorption ability and plant growth (particularly germination rate) and better balance between them, the substitution rate of the carboxyl groups is preferably 10 mol% to less than 100 mol%, more preferably 15 mol% to 90 mol%, and particularly preferably 15 mol% to 80 mol%. With such a substitution rate, plant growth (particularly germination rate) can be further improved while maintaining a moderate water retention capacity (e.g., deionized water CRC).
[0132] [8-2] Fibrous materials The fibrous material is not particularly limited, and materials that are normally used for the desired application (for example, sanitary materials (hygienic products) such as paper diapers, sanitary napkins, incontinence products for adults (incontinence pads), and pet sheets, soil water retention agents for agricultural and horticultural use, and industrial water-stopping agents) can be used. Specifically, wood pulp fibers such as mechanical pulp, chemical pulp, semi-chemical pulp, and dissolving pulp from wood, and artificial cellulose fibers such as rayon and acetate can be used. Synthetic polymer fibers such as polyolefin, polyester, polyacrylonitrile, and nylon can also be used. A mixture of multiple fiber types mentioned above can also be used.
[0133] The content of the fibrous material in the water absorbent resin composition is, for example, 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, even more preferably more than 0.1 parts by mass, and particularly preferably 0.5 parts by mass or more, relative to 100 parts by mass of the water absorbent resin composition. If it is within the above range, the fibrous material can capture the sprayed water sufficiently and efficiently. In addition, the content of the fibrous material in the water absorbent resin composition is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, even more preferably 20 parts by mass or less, and particularly preferably 15 parts by mass or less, relative to 100 parts by mass of the water absorbent resin composition. If it is within the above range, a sufficient amount of water absorbent resin is present, so that a sufficient amount of water can be captured (sufficient deionized water CRC can be secured).
[0134] In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.01 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.01 parts by mass or more and 25 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.01 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.01 parts by mass or more and 15 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.05 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.05 parts by mass or more and 25 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.05 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.05 parts by mass or more and 15 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.1 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.1 parts by mass or more and 25 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.1 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.1 parts by mass or more and 15 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is more than 0.1 parts by mass and not more than 30 parts by mass with respect to 100 parts by mass of the water absorbent resin composition.In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is more than 0.1 parts by mass and not more than 25 parts by mass with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is more than 0.1 parts by mass and not more than 20 parts by mass with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is more than 0.1 parts by mass and not more than 15 parts by mass with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.5 parts by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.5 parts by mass or more and 25 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition. In one embodiment of the present invention, the content of the fibrous material in the water absorbent resin composition is 0.5 parts by mass or more and 15 parts by mass or less with respect to 100 parts by mass of the water absorbent resin composition.
[0135] The measurement of the content of the fibrous material in the water-absorbent resin composition is not particularly limited, and a known method can be used. Specifically, when the water-absorbent resin composition is composed of a water-absorbent resin and a fibrous material, and the fibrous material is pulp, i) A method in which water and cobalt chloride are added to a mixture (water absorbent resin composition) of a water absorbent resin and a fibrous material to selectively color the water absorbent resin, the mixture is shaken in a separating funnel, and the water absorbent resin and the fibrous material are separated and collected by utilizing the difference in sedimentation speed between the water absorbent resin and the fibrous material, the collected materials are each dried, and the masses of the water absorbent resin and the fibrous material are measured; ii) A method in which water and a pulp-decomposing enzyme such as cellulase are added to a mixture of a water-absorbent resin and a fibrous material (a water-absorbent resin composition) to solubilize only the pulp, and then the remaining water-absorbent resin is quantified by filtration or the like, and the amount of the pulp is determined as the amount of the reduced amount; and iii) A method in which a solubilizer (e.g., permanganate, hydrogen peroxide-cobalt salt, hydrogen peroxide-copper salt; Journal of the National Institute of Environmental Science, Vol. 36, No. 1 (2011) P. 51-58) that solubilizes water and the water absorbent resin is added to a mixture of a water absorbent resin and a fibrous material (water absorbent resin composition), and only the water absorbent resin is solubilized, and then the remaining pulp is quantified by filtration. can be used.
[0136] The contents of the fibrous material measured by the above methods i) to iii) are substantially the same. In this specification, the amount measured by the above method iii) is defined as the content of the fibrous material in the water absorbent resin composition.
[0137] In addition, when the water absorbent resin as a raw material contains fibrous material, the content of the fibrous material in the water absorbent resin is quantified by the above-mentioned method, and the total amount including the amount of the fibrous material added later may be regarded as the content of the fibrous material in the water absorbent resin composition.
[0138] The size of the fibrous material is not particularly limited. The length (number average fiber length) of the fibrous material is, for example, 0.1 mm or more and 20 mm or less, preferably 0.2 mm or more and 15 mm or less, more preferably 0.3 mm or more and 10 mm or less, and particularly preferably 0.4 mm or more and 5.0 mm or less. With such a fiber length, the fibrous material can be mixed more homogeneously with the water absorbent resin.
[0139] In this specification, the length of the fibrous material (number average fiber length) is a value measured according to the following method. The fibrous material was photographed using a scanning electron microscope (Keyence Corporation: VF-9800) at a magnification of 5 to 100 times. From the photographed image, 50 points in the sample were randomly selected, and the fiber length of each was measured, and the average value was calculated, and this average value was taken as the length of the fibrous material (number average fiber length).
[0140] [8-3] Other ingredients The water absorbent resin composition according to the present embodiment essentially contains a water absorbent resin and a fibrous material, but may further contain other components in addition to the above. Preferably, the water absorbent resin composition is substantially composed of a water absorbent resin and a fibrous material (the total content of the water absorbent resin and the fibrous material in the water absorbent resin composition is more than 90 mass%, preferably more than 95 mass%). Particularly preferably, the water absorbent resin composition is composed of a water absorbent resin and a fibrous material (the total content of the water absorbent resin and the fibrous material in the water absorbent resin composition is 100 mass%).
[0141] [9] Physical properties of water-absorbent resin composition The water-absorbent resin composition according to the present invention includes a water-absorbent resin having carboxyl groups, and a part of the carboxyl groups being substituted with at least one element selected from the group consisting of potassium element and nitrogen element at a substitution rate of 5 mol % or more and 100 mol % or less, and a fibrous material.
[0142] When the water-absorbent resin composition according to the present invention is used as a water-retaining material, it is desirable to satisfy at least one of the following [9-1], the following [9-2], and the following [9-3], more desirably at least two, and most desirably all of them.
[0143] [9-1] Water soluble matter (16-hour value) The water absorbent resin composition according to the present invention preferably has a small water-soluble content (16-hour value). In one embodiment, the water-soluble content (16-hour value) of the water absorbent resin composition according to the present invention or the water retention agent containing the water absorbent resin composition is less than 17% by mass. In one embodiment, the water-soluble content (16-hour value) of the water absorbent resin composition or the water retention agent containing the water absorbent resin composition is 16.0% by mass or less, 15.0% by mass or less, 14.0% by mass or less, 13.0% by mass or less, 12.0% by mass or less, or 11.0% by mass or less (lower limit: 0% by mass). By setting the water-soluble content at such a level, when the water absorbent resin composition is used for sanitary materials, the toughness of the polymer structure can be improved, and the process damage resistance and water absorption properties (particularly AAP0.3) can be improved. In addition, when the water absorbent resin composition is used as a water retention material for plant growth, the change in water absorption properties due to the external environment such as soil can be further suppressed and prevented.
[0144] [9-2] Residual monomer amount The water absorbent resin composition according to the present invention has a small amount of residual monomers. In one embodiment, the amount of residual monomers in the water absorbent resin composition according to the present invention or in the water retention agent containing the water absorbent resin composition is 100 mass ppm or less. In one embodiment, the amount of residual monomers in the water absorbent resin composition or in the water retention agent containing the water absorbent resin composition is 80 mass ppm or less, 70 mass ppm or less, 60 mass ppm or less, 50 mass ppm or less, 40 mass ppm or less, 30 mass ppm or less, or less than 30 mass ppm (lower limit: 0 mass ppm). By setting the amount of residual monomers to such an amount, low skin irritation can be expected when the water absorbent resin composition is used for sanitary materials. In addition, when used as a water retention material for plant growth, a water absorbent resin composition with even better safety can be provided.
[0145] [9-3] Deionized water CRC (absorption capacity without pressure) The absorbency without pressure (deionized water CRC) of the water absorbent resin composition according to the present invention is usually 5 g / g or more, preferably 50 g / g or more, more preferably 60 g / g or more, even more preferably more than 70 g / g, and particularly preferably 80 g / g or more. There is no particular limit to the upper limit, and a higher deionized water CRC is preferable, but from the viewpoint of balance with other physical properties, it is preferably 500 g / g or less, more preferably 450 g / g or less, and even more preferably 400 g / g or less. By setting the absorbency without pressure (deionized water CRC) at such a level, sufficient water retention can be ensured when used as a water retention material for plant growth.
[0146]
[10] A method for producing a water-absorbing resin composition according to one embodiment of the seventh aspect The water absorbent resin composition according to this embodiment can be produced in the same manner as in [2] above, except that the substitution rate of the carboxyl group is within the above range. That is, in one embodiment of the present invention, the method for producing the water absorbent resin composition of the present invention comprises treating a raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salt, lithium salt, magnesium salt, calcium salt and iron salt of a carboxyl group with an acidic substance (acid treatment step); adding a substance containing at least one element selected from the group consisting of potassium element and nitrogen element to the raw water absorbent resin treated with the acidic substance in an amount such that the substitution rate of the carboxyl group is 5 mol% or more and 100 mol% or less, thereby substituting the carboxyl group present in the raw water absorbent resin with the element (substitution step).
[0147] [10-1] Pretreatment process Before the raw water absorbent resin is treated with an acidic substance, other treatments such as a washing / sterilization step, a crushing step, a separation step, and a dehydration step may be performed (pretreatment step). This step is the same as the above [2-1].
[0148] [10-2] Acid treatment process If necessary, after the pretreatment in the above [10-1], the raw water absorbent resin is treated with an acidic substance (acid treatment step). By this step, the salt of the carboxyl group in the raw water absorbent resin (-COOX or -COO-Y-OOC-; X is sodium, potassium or lithium, and Y is an alkaline earth metal or a transition metal (e.g., magnesium, calcium, iron, etc.)) is converted to a carboxyl group (-COOH). This step is the same as the above [2-2].
[0149] [10-3] Cleaning process The acid-treated raw water absorbent resin may be washed. In one embodiment of the present invention, the acid-treated raw water absorbent resin is washed with water to obtain a raw water absorbent resin washed with water. This step can remove or reduce the content of impurities (e.g., acidic substances, polyvalent metal ions) present on the surface, inside, or in gaps between particles of the acid-treated raw water absorbent resin, thereby improving the water absorption performance (e.g., deionized water CRC) of the final product, the regenerated water absorbent resin. This step is the same as the above [2-3].
[0150] [10-4] Substitution process (neutralization process) In this step, a substance containing at least one element selected from the group consisting of potassium and nitrogen elements (K / N-containing substance) is added to the raw water absorbent resin treated in the acid treatment step [10-2] or the washing step [10-3] in such an amount that the substitution rate of the carboxyl groups is 5 mol % or more and 100 mol % or less. As a result, of all the carboxyl groups present in the raw water absorbent resin (raw polymer) after the acid treatment, hydrogen atoms of carboxyl groups (-COOH) at a ratio of 5 mol % or more and 100 mol % or less are substituted (neutralized) with potassium elements (-COOK) or nitrogen elements. Regarding the nitrogen element, from the viewpoints that the carboxyl groups are easily substituted and that the regenerated water absorbent resin is easily utilized by plants when used as a water retention material for plant growth, etc., it is preferable that the carboxyl groups (-COOH) are substituted (neutralized) with ammonium ions (-COO - NH4 + ) is preferably converted (substituted).
[0151] Here, the amount of the K / N-containing substance added is such that the substitution rate of the carboxyl group is 5 mol% or more and 100 mol% or less, and the preferred amount is such that the substitution rate of the carboxyl group is the ratio described in [8-1] above. This step is the same as [2-4] above, except that the amount of the K / N-containing substance added is such that the substitution rate of the carboxyl group is the above-mentioned.
[0152] [10-5] Other processes In addition to the above-mentioned steps, the production method according to the present invention may further include a drying step, a pulverizing step, a classification step, a surface cross-linking step, a sizing step, and the like, as necessary.
[0153] [10-5-1] Drying process This step is a step of obtaining a dried polymer by drying the water-absorbent resin to a desired resin solid content. This step is the same as the above-mentioned [2-5-1].
[0154] [10-5-2] Crushing process This step is a step of pulverizing (and classifying, if necessary) the water-absorbent resin or the dried product obtained in the above drying step. This step is the same as the above [2-5-2].
[0155] [10-5-3] Classification process A classification step may be carried out after the pulverization. This step is the same as that in [2-5-3] above.
[0156] [10-5-4] Surface crosslinking step This step is a step of providing a part with a higher crosslink density on the surface layer (particularly, a part several tens of μm from the surface of the water-absorbent resin precursor) of the water-absorbent resin or the water-absorbent resin obtained through any of the steps described above (hereinafter, also simply referred to as "water-absorbent resin precursor"), and may be composed of a mixing step, a heat treatment step, and a cooling step (optional). In the surface crosslinking step, a surface-crosslinked water-absorbent resin is obtained by radical crosslinking on the surface of the water-absorbent resin precursor, surface polymerization, crosslinking reaction with a surface crosslinking agent, etc. This step is the same as the above [2-5-4].
[0157] [10-5-5] Sizing process This step is a step of adjusting the particle size of the surface cross-linked water absorbent resin. This particle size adjustment step provides a water absorbent resin whose particle size or particle size distribution is more actively controlled. This step is the same as the above [2-5-5].
[0158] As described above, the water-absorbent resin contained in the water-absorbent resin composition is the same as that described in [2] above, except for the substitution rate of the carboxyl group.
[0159] [10-6] Fibrous material addition process In this embodiment, the location of addition of the fibrous material is not particularly limited. The fibrous material may be added before, during, or after any of the steps of the above [10-1] pretreatment step, the above [10-2] acid treatment step, the above [10-3] washing step, the above [10-4] substitution step (neutralization step), or the above [10-5] other steps (the above [10-5-1] drying step, the above [10-5-2] pulverization step, the above [10-5-3] classification step, the above [10-5-4] surface cross-linking step, or the above [10-5-5] sizing step). Among these, from the viewpoint of suppressing the loss of the fibrous material during the operation, it is preferable to add the fibrous material before the above [10-5] other steps. Alternatively, in the case of using a water absorbent resin that does not substantially contain fibrous impurities (content of fibrous material=less than 0.01% by mass, preferably less than 0.005% by mass), from the viewpoints of improving workability, higher accuracy of the amount of fibrous material added, and a balance between these, it is preferable to add the fibrous material before the above-mentioned [10-2] acid treatment step, or after the above-mentioned [10-4] substitution step (neutralization step); after the above-mentioned [10-1] pretreatment step, before the above-mentioned [10-2] acid treatment step, after the above-mentioned [10-5-3] classification step, It is more preferable to add the fibrous material before the surface cross-linking step [10-5-4], or after the surface cross-linking step [10-5-4] and before the sizing step [10-5-5], it is even more preferable to add the fibrous material after the classification step [10-5-3] and before the surface cross-linking step [10-5-4], or after the surface cross-linking step [10-5-4] and before the sizing step [10-5-5], it is particularly preferable to add the fibrous material after the surface cross-linking step [10-5-4] and before the sizing step [10-5-5]. In addition, when using a water-absorbing resin recovered from used paper diapers, it is preferable to add the fibrous material before the acid treatment step [10-2].
[0160] In this step, the amount of fibrous material added is preferably the amount described in the above section [8-2] Fibrous material.
[0161]
[11] Water-retaining material according to one embodiment of the eighth aspect The water absorbent resin composition according to one embodiment of the sixth aspect, or the water absorbent resin composition produced by one embodiment of the seventh aspect, can be suitably used as a water retention material for plant growth.
[0162] In one embodiment of the eighth aspect, there is provided a water retention material comprising or consisting of the water absorbent resin composition according to the present invention.
[0163] In the present embodiment, in the water-retaining material according to one embodiment of the fifth aspect of the above [7], the recycled water-absorbent resin can be read as the water-absorbent resin composition according to the present invention, and the water-retaining material can be similar to the water-retaining material.
[0164] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims.
[0165] The present invention encompasses the following aspects and configurations.
[0166] 1. A raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salts, potassium salts, lithium salts, magnesium salts, calcium salts, and iron salts of a carboxyl group is treated with an acidic substance; a method for producing a regenerated water absorbent resin, comprising: adding a substance containing at least one element selected from the group consisting of potassium element and nitrogen element to the raw water absorbent resin treated with the acidic substance in such an amount that the substitution rate of the carboxyl groups is more than 5 mol % and less than 40 mol %, thereby substituting the carboxyl groups present in the raw water absorbent resin with the element; 2. The raw water absorbent resin is made from used absorbent articles or waste from the water absorbent resin manufacturing process. The method according to claim 1, wherein the water absorbent resin is recovered from the 3. The raw water absorbent resin is a recovered water absorbent resin recovered from a used absorbent article, which contains a polymer having a sodium salt, a potassium salt, and / or a lithium salt of a carboxyl group; The method according to 1 or 2 above, wherein the raw water absorbent resin is dehydrated and then treated with the acidic substance; 4. A method for producing a water-absorbing resin, comprising producing a recycled water-absorbing resin by using the method according to any one of 1. to 3. above, and producing a water-absorbing resin by using the recycled water-absorbing resin as a part of a raw material; 5. A method for producing a water-retaining material, comprising producing a recycled water-absorbent resin by using the method according to any one of 1. to 3. above; 6. A water-absorbent resin recycled from a used absorbent article or waste from a water-absorbent resin production process, comprising a polymer having carboxyl groups and in which a part of the carboxyl groups is substituted with at least one element selected from the group consisting of potassium and nitrogen; 7. The recycled water absorbent resin according to 6. above, wherein the carboxyl group of the polymer is substituted with potassium element at a substitution rate of more than 5 mol % and less than 40 mol %; 8. The recycled water absorbent resin according to 6. or 7., wherein the carboxyl group of the polymer is substituted with nitrogen element at a substitution rate of more than 5 mol % and less than 40 mol %; 9. The recycled water absorbent resin according to any one of 6. to 8., wherein the polymer has an ammonium salt (-COONH4) of a carboxyl group at a substitution rate of more than 5 mol% and less than 40 mol%; 10. The recycled water absorbent resin according to any one of 6. to 9., which has a water-soluble content of 20 mass% or less; 11. The recycled water absorbent resin according to any one of 6. to 10., wherein the amount of residual monomer is 100 ppm by mass or less; 12. A water-retaining material comprising or consisting of the recycled water-absorbent resin according to any one of 6. to 11. above; 13. A water-absorbent resin composition comprising a water-absorbent resin having carboxyl groups, and a part of the carboxyl groups being substituted with at least one element selected from the group consisting of potassium and nitrogen at a substitution rate of 5 mol % or more and 100 mol % or less, and a fibrous material; 14. The water-absorbent resin composition according to 13 above, wherein the fibrous material is contained in an amount of 0.01 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the water-absorbent resin composition; 15. A water-retaining material comprising or consisting of the water-absorbent resin composition according to 13. or 14. above; 16. A raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salts, lithium salts, magnesium salts, calcium salts, and iron salts of a carboxyl group is treated with an acidic substance; a method for producing a water absorbent resin composition according to any one of the above 13. to 15., comprising adding a substance containing at least one element selected from the group consisting of potassium element and nitrogen element to the raw water absorbent resin treated with the acidic substance in such an amount that a substitution rate of the carboxyl group is 5 mol % or more and 100 mol % or less, thereby substituting the carboxyl group present in the raw water absorbent resin with the element; 17. The method according to claim 16, wherein the raw absorbent resin is a recovered absorbent resin recovered from used absorbent articles or waste from a process for producing the absorbent resin. EXAMPLES
[0167] The effects of the present invention will be described using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples, and examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention. In the following examples, unless otherwise specified, operations were performed at room temperature (25°C). Furthermore, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.
[0168] [Manufacturing example a] A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 1.83 g of 1.0 mass % trisodium diethylenetriaminepentaacetate (DTPA·3Na), 99.5 g of 48.5 mass % aqueous sodium hydroxide solution, and 387.5 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (a').
[0169] Next, the monomer aqueous solution (a') was cooled while stirring. When the liquid temperature reached 40.0°C, 96.7 g of 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare the monomer aqueous solution (a). At this time, the temperature of the monomer aqueous solution (a) rose to 78.0°C due to the heat of neutralization in the second stage. Immediately after starting to add the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and eventually became a transparent homogeneous solution.
[0170] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred aqueous solution of monomer (a), and the mixture was immediately poured into a stainless steel bat-shaped container (bottom surface 340×340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second stage neutralization to pouring the aqueous solution of monomer (a) into the bat-shaped container was 55 seconds, and the bat-shaped container was heated using a hot plate until the surface temperature reached 40° C. The polymerization reaction started 60 seconds after the aqueous solution of monomer (a) was poured into the bat-shaped container. The polymerization reaction proceeded by expanding and foaming in all directions while generating steam, and then contracted to a size slightly larger than that of the bat-shaped container. After 3 minutes had passed since the start of the polymerization reaction, the hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") (a) was taken out. The series of operations was carried out in an open-air system.
[0171] The hydrogel (a) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm, and then the hydrogel (a) was spread on a 50-mesh wire net and dried with hot air at 190° C. for 60 minutes. The hydrogel was then crushed with a vibration mill and further classified with JIS standard sieves having openings of 850 μm and 150 μm to obtain an irregularly crushed water-absorbent resin precursor (a).
[0172] 100 parts by mass of the obtained water absorbent resin precursor (a) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was heated at 100°C for 45 minutes.
[0173] After that, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (a). The obtained water-absorbent resin (a) had a CRC of 35.9 g / g, an AAP0.3 of 29.4 g / g, and a water-soluble content (16-hour value) of 17.1 mass%. The neutralization rate of the obtained water-absorbent resin (a) was about 70 mol%.
[0174] Next, 3000 parts by mass of artificial urine (urea 1.9% by mass, sodium chloride 0.80% by mass, magnesium chloride hexahydrate 0.10% by mass, calcium chloride dihydrate 0.10% by mass, ion-exchanged water 97.1% by mass) was added to 100 parts by mass of the water-absorbent resin (a), mixed, and left at room temperature for 12 hours or more. Thus, a simulated used water-absorbent resin (a) was obtained as a raw water-absorbent resin.
[0175] [Manufacturing example b] 99.0 parts by mass of the water-absorbent resin (a) obtained in Production Example a and 1.0 part by mass of pulp fiber (pulp fiber extracted from the absorbent part of "GOOON (registered trademark)" manufactured by Daio Paper Corporation, which is a commercially available paper diaper; number average fiber length: 2.5 mm) (fibrous material) were thoroughly mixed in a container equipped with a stirring blade to obtain a water-absorbent resin composition (1).
[0176] To 100 parts by mass of this water absorbent resin composition (1), 3,000 parts by mass of artificial urine (urea 1.9% by mass, sodium chloride 0.80% by mass, magnesium chloride hexahydrate 0.10% by mass, calcium chloride dihydrate 0.10% by mass, ion-exchanged water 97.1% by mass) was added, and the mixture was left at room temperature for 12 hours or more to obtain a simulated used water absorbent resin composition (b).
[0177] [Manufacturing example c] 90.0 parts by mass of the water absorbent resin (a) obtained in Production Example a and 10.0 parts by mass of pulp fibers (pulp fibers extracted from the absorbent part of "GOOON (registered trademark)" manufactured by Daio Paper Corporation, a commercially available paper diaper, number average fiber length 2.5 mm) (fibrous material) were thoroughly mixed in a container equipped with a stirring blade to obtain a water absorbent resin composition (2).
[0178] To 100 parts by mass of this water absorbent resin composition (2), 3,000 parts by mass of artificial urine (urea 1.9% by mass, sodium chloride 0.80% by mass, magnesium chloride hexahydrate 0.10% by mass, calcium chloride dihydrate 0.10% by mass, ion-exchanged water 97.1% by mass) was added, and the mixture was left at room temperature for 12 hours or more to obtain a simulated used water absorbent resin composition (c).
[0179] [Manufacturing example d] 78.0 parts by mass of the water absorbent resin (a) obtained in Production Example a and 22.0 parts by mass of pulp fibers (pulp fibers extracted from the absorbent portion of a commercially available disposable diaper ("GOON (registered trademark)" manufactured by Daio Paper Co., Ltd., number average fiber length 2.5 mm) (fibrous material) were thoroughly mixed in a container equipped with a stirring blade to obtain a water absorbent resin composition (3).
[0180] To 100 parts by mass of this water absorbent resin composition (3), 3,000 parts by mass of artificial urine (urea 1.9% by mass, sodium chloride 0.80% by mass, magnesium chloride hexahydrate 0.10% by mass, calcium chloride dihydrate 0.10% by mass, ion-exchanged water 97.1% by mass) was added, and the mixture was left at room temperature for 12 hours or more to obtain a simulated used water absorbent resin composition (d).
[0181] [Example 1] 100 parts by mass of the simulated used water absorbent resin (a) (solid content 3.23% by mass) obtained in Production Example a and 242 parts by mass of a 3.0% by mass aqueous citric acid solution (corresponding to about 3.1 moles of carboxyl groups of citric acid per mole of carboxyl groups of the water absorbent resin) were added to a reaction vessel equipped with an agitator, and the mixture was stirred for 15 minutes (acid treatment). The acid treatment converted all sodium salts (-COONa) of carboxyl groups present in the simulated used water absorbent resin (a) to carboxyl groups (-COOH). Furthermore, the acid treatment caused the simulated used water absorbent resin (a) to release more water than in the state before the acid treatment, and it was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0182] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, to which 323 parts by mass of deionized water was added and stirred for 15 minutes (water washing treatment).
[0183] Next, the reaction vessel content after the water washing treatment is filtered through a 100 mesh stainless steel wire screen, and the filtrate is returned to the reaction vessel again. % aqueous potassium hydroxide solution (1.54 parts by mass, equivalent to a substitution rate of 15 mol%) was dropped (substitution treatment). After the completion of the dropping, the mixture was left to stand for 30 minutes to obtain a neutralized water-absorbent resin in the form of a hydrous gel (regenerated water-absorbent resin (1)).
[0184] The neutralized water-absorbent resin in the form of a hydrous gel (regenerated water-absorbent resin (1)) was placed in a vacuum dryer adjusted to a temperature of 60° C., dried for 18 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining an irregularly pulverized water-absorbent resin precursor (1).
[0185] 100 parts by mass of the obtained water absorbent resin precursor (1) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was heated at 100° C. for 45 minutes.
[0186] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (1). The physical properties of the recycled water absorbent resin (1) are shown in Table 1.
[0187] [Example 2] The same operation as in Example 1 was carried out except that the amount of the 20% by mass aqueous potassium hydroxide solution used in the substitution treatment was changed from 1.54 parts by mass to 3.59 parts by mass (corresponding to a substitution rate of 35 mol%) in Example 1, to obtain a recycled water absorbent resin (2). The physical properties of the recycled water absorbent resin (2) are shown in Table 1.
[0188] [Example 3] The same operation as in Example 1 was carried out except that the replacement treatment was carried out by adding 0.26 parts by mass of ammonium carbonate powder (corresponding to a replacement rate of 15 mol%) to the filtrate, to obtain a recycled water absorbent resin (3). The physical properties of the recycled water absorbent resin (3) are shown in Table 1.
[0189] [Example 4] A recycled water absorbent resin (4) was obtained by the same operation as in Example 3, except that the amount of ammonium carbonate powder used in the substitution treatment was changed from 0.26 parts by mass to 0.62 parts by mass (corresponding to a substitution rate of 35 mol%) in Example 3. The physical properties of the recycled water absorbent resin (4) are shown in Table 1.
[0190] [Example 5] A simulated used water absorbent resin (a) was produced in the same manner as in Production Example a.
[0191] 100 parts by mass of this simulated used water absorbent resin (a) (solid content 3.23% by mass) and 120 parts by mass of a 1.7% by mass aqueous calcium chloride solution were added to a reaction vessel equipped with a stirring blade, and stirred for 15 minutes (dehydration treatment). The dehydration treatment caused the simulated used water absorbent resin (a) to release more water than before the dehydration treatment, and the resin was in a shrunk state.
[0192] The content of the reaction vessel after the dehydration treatment was filtered through a 100-mesh stainless steel wire screen, and the filtered matter was returned to the reaction vessel again. 134 parts by mass of a 1.0% by mass hydrochloric acid aqueous solution (corresponding to about 1.0 mol per 1 mol of -COONa groups) was added thereto, and the mixture was stirred for 15 minutes (acid treatment).
[0193] Next, the content of the reaction vessel after the acid treatment is filtered through a 100 mesh stainless steel wire mesh, and the obtained unneutralized filtrate is returned to the reaction vessel again. While stirring the filtrate, 3.59 parts by mass of a 20% by mass aqueous solution of potassium hydroxide (corresponding to a substitution rate of 35 mol%) was dropped thereto (substitution treatment). After the completion of the dropping, the mixture was left to stand for 30 minutes to obtain a neutralized water-absorbent resin (regenerated water-absorbent resin (5)) in a hydrous gel state.
[0194] The neutralized water absorbent resin in the form of a hydrous gel (regenerated water absorbent resin (5)) was placed in a vacuum dryer adjusted to a temperature of 60° C., dried for 18 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining an irregularly pulverized water absorbent resin precursor (5).
[0195] 100 parts by mass of the obtained water absorbent resin precursor (5) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water, and the mixture was heated at 100° C. for 45 minutes.
[0196] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (5). The physical properties of the recycled water absorbent resin (5) are shown in Table 1.
[0197] [Example 6] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin composition (b) (containing 3.19 parts by mass of water absorbent resin solid content) and 242 parts by mass of a 3.0% by mass aqueous citric acid solution (corresponding to about 3.1 moles of carboxyl groups of citric acid per mole of carboxyl groups of the water absorbent resin) were added, and the mixture was stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin composition (b) after the acid treatment released more water than before the treatment and was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0198] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0199] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100-mesh stainless steel wire net, and the filtrate was returned to the reaction vessel again, and 1.53 parts by mass of a 20% by mass potassium hydroxide aqueous solution (corresponding to a substitution rate of 15 mol%) was dropped into the filtrate while stirring it (substitution treatment). After the dropping was completed and the mixture was left to stand for 30 minutes, a water-containing neutralized water absorbent resin composition (regenerated water absorbent resin composition) was obtained.
[0200] The neutralized water-absorbent resin composition in a hydrated state (regenerated water-absorbent resin composition) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining a water-absorbent resin composition precursor (6) having an average particle size of 360 μm that passed through the sieve with mesh sizes of 850 μm and remained on the sieve with mesh sizes of 106 μm.
[0201] 100 parts by mass of the obtained water absorbent resin composition precursor (6) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water, and the mixture was subjected to heat treatment at 100°C for 45 minutes.
[0202] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water-absorbent resin composition (6). The physical properties of the recycled water-absorbent resin composition (6) are shown in Table 1.
[0203] [Example 7] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin composition (b) (containing 3.19 parts by mass of water absorbent resin solid content) and 242 parts by mass of a 3.0 mass% aqueous citric acid solution were added and stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin composition (b) after the acid treatment released more water than in the state before the treatment and was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0204] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0205] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100-mesh stainless steel wire net, and the filtrate was returned to the reaction vessel again, and 3.56 parts by mass of a 20% by mass potassium hydroxide aqueous solution (equivalent to a substitution rate of 35 mol%) was dropped into the filtrate while stirring it (substitution treatment). After the dropping was completed, the mixture was left to stand for 30 minutes, and then a water-containing neutralized water absorbent resin composition (regenerated water absorbent resin composition) was obtained.
[0206] The neutralized water-absorbent resin composition in a hydrated state (regenerated water-absorbent resin composition) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining a water-absorbent resin composition precursor (7) having an average particle size of 360 μm that passed through the sieve with mesh sizes of 850 μm and remained on the sieve with mesh sizes of 106 μm.
[0207] 100 parts by mass of the obtained water absorbent resin composition precursor (7) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water, and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0208] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (7). The physical properties of the recycled water absorbent resin composition (7) are shown in Table 1.
[0209] [Example 8] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin composition (b) (containing 3.19 parts by mass of water absorbent resin solid content) and 242 parts by mass of a 3.0 mass% aqueous citric acid solution were added and stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin composition (b) after the acid treatment released more water than in the state before the treatment and was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0210] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0211] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100-mesh stainless steel wire net, and the filtrate was returned to the reaction vessel again, and 7.22 parts by mass of a 20% by mass potassium hydroxide aqueous solution (corresponding to a substitution rate of 70 mol%) was dropped into the filtrate while stirring it (substitution treatment). After the dropping was completed and the mixture was left to stand for 30 minutes, a water-containing neutralized water absorbent resin composition (regenerated water absorbent resin composition) was obtained.
[0212] The neutralized water-absorbent resin composition in a hydrated state (regenerated water-absorbent resin composition) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining a water-absorbent resin composition precursor (8) having an average particle size of 360 μm that passed through the sieve with mesh sizes of 850 μm and remained on the sieve with mesh sizes of 106 μm.
[0213] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin composition precursor (8), and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0214] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water-absorbent resin composition (8). The physical properties of the recycled water-absorbent resin composition (8) are shown in Table 1.
[0215] [Example 9] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin composition (b) (containing 3.19 parts by mass of water absorbent resin solid content) and 242 parts by mass of a 3.0 mass% aqueous citric acid solution were added and stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin composition (b) after the acid treatment released more water than in the state before the treatment and was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0216] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0217] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100 mesh stainless steel wire net, and the filtered matter was returned to the reaction vessel again, and 1.24 parts by mass of ammonium carbonate powder (corresponding to a substitution rate of 70 mol%) was dropped into the filtered matter while stirring it (substitution treatment). After the dropping was completed, the mixture was left to stand for 30 minutes, and then a water-containing neutralized water absorbent resin composition (regenerated water absorbent resin composition) was obtained.
[0218] The neutralized water-absorbent resin composition in a hydrated state (regenerated water-absorbent resin composition) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining a water-absorbent resin composition precursor (9) having an average particle size of 360 μm that passed through the sieve with mesh sizes of 850 μm and remained on the sieve with mesh sizes of 106 μm.
[0219] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin composition precursor (9), and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0220] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (9). The physical properties of the recycled water absorbent resin composition (9) are shown in Table 1.
[0221] [Example 10] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin composition (c) (containing 2.90 parts by mass of water absorbent resin solid content) and 242 parts by mass of a 3.0% by mass aqueous citric acid solution (corresponding to about 3.4 moles of carboxyl groups of citric acid per mole of carboxyl groups of the water absorbent resin) were added, and the mixture was stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin composition (c) after the acid treatment released more water than before the treatment and was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0222] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0223] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100 mesh stainless steel wire net, and the filtrate was returned to the reaction vessel again, and 6.56 parts by mass of a 20% by mass potassium hydroxide aqueous solution (corresponding to a substitution rate of 70 mol%) was dropped into the filtrate while stirring it (substitution treatment). After the dropping was completed, the mixture was left to stand for 30 minutes, and then a water-containing neutralized water absorbent resin composition (regenerated water absorbent resin composition) was obtained.
[0224] The neutralized water-absorbent resin composition in a hydrated state (regenerated water-absorbent resin composition) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining a water-absorbent resin composition precursor (10) having an average particle size of 360 μm that passed through the sieve with mesh sizes of 850 μm and remained on the sieve with mesh sizes of 106 μm.
[0225] 100 parts by mass of the obtained water absorbent resin composition precursor (10) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water, and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0226] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (10). The physical properties of the recycled water absorbent resin composition (10) are shown in Table 1.
[0227] [Example 11] 100 parts by mass of the simulated used water absorbent resin (a) (3.19 parts by mass of water absorbent resin solid content) and 242 parts by mass of 3.0% by mass citric acid aqueous solution (equivalent to about 3.1 moles of carboxyl groups of citric acid per mole of carboxyl groups of the water absorbent resin) were added to a reaction vessel equipped with a stirring blade and an acid treatment was performed by stirring for 15 minutes. The simulated used water absorbent resin (a) after the acid treatment released more water than before the treatment and was in a shrunk state (the acid treatment using the citric acid aqueous solution also served as a dehydration treatment).
[0228] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0229] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100 mesh stainless steel wire net, and the filtered matter was returned to the reaction vessel again, and 7.22 parts by mass of a 20% by mass potassium hydroxide aqueous solution (corresponding to a substitution rate of 70 mol%) was dropped into the filtered matter while stirring (substitution treatment). After the dropping was completed, the mixture was left to stand for 30 minutes, and then a neutralized water-containing absorbent resin (regenerated water-absorbent resin) was obtained.
[0230] The neutralized water-absorbent resin in a hydrated state (regenerated water-absorbent resin) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining a water-absorbent resin precursor (11) having an average particle size of 360 μm that passed through the sieve with mesh sizes of 850 μm and remained on the sieve with mesh sizes of 106 μm.
[0231] 99.0 parts by mass of the obtained water absorbent resin precursor (11) and 1.0 part by mass of pulp fiber (pulp fiber extracted from the absorbent part of a commercially available disposable diaper ("GOON (registered trademark)" manufactured by Daio Paper Co., Ltd.) (fibrous material) were thoroughly mixed in a container equipped with a stirring blade to obtain a water absorbent resin composition precursor (11).
[0232] 100 parts by mass of the obtained water absorbent resin composition precursor (11) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water, and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0233] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (11). The physical properties of the recycled water absorbent resin composition (11) are shown in Table 1.
[0234] [Example 12] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin (a) (water absorbent resin solid content 3.19 parts by mass) and 242 parts by mass of a 3.0 mass% citric acid aqueous solution were added and stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin (a) after the acid treatment released more water than in the state before the treatment and was in a shrunk state (the acid treatment with the citric acid aqueous solution also served as a dehydration treatment).
[0235] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0236] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100 mesh stainless steel wire net, and the filtered matter was returned to the reaction vessel again, and 7.22 parts by mass of a 20% by mass potassium hydroxide aqueous solution (corresponding to a substitution rate of 70 mol%) was dropped into the filtered matter while stirring (substitution treatment). After the dropping was completed, the mixture was left to stand for 30 minutes, and then a neutralized water-containing absorbent resin (regenerated water-absorbent resin) was obtained.
[0237] The neutralized water-absorbent resin in a hydrated state (regenerated water-absorbent resin) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm, thereby obtaining a water-absorbent resin precursor (12) having an average particle size of 360 μm that passed through the sieve with mesh sizes of 850 μm and remained on the sieve with mesh sizes of 106 μm.
[0238] 100 parts by mass of the obtained water absorbent resin precursor (12) was uniformly mixed with a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water, and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0239] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin (12).
[0240] 99.0 parts by mass of the recycled water absorbent resin (12) and 1.0 part by mass of pulp fiber (fibrous material) (pulp fiber extracted from the absorbent part of a commercially available paper diaper ("Goon (registered trademark)" manufactured by Daio Paper Co., Ltd.)) were thoroughly mixed in a container equipped with a stirring blade to obtain a recycled water absorbent resin composition (12). The physical properties of the recycled water absorbent resin composition (12) are shown in Table 1.
[0241] [Example 13] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin composition (d) (containing 2.52 parts by mass of water absorbent resin solid content) and 242 parts by mass of a 3.0% by mass aqueous citric acid solution (corresponding to about 3.9 moles of carboxyl groups of citric acid per mole of carboxyl groups of the water absorbent resin) were added, and the mixture was stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin composition (d) after the acid treatment released more water than before the treatment and was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0242] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0243] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100-mesh stainless steel wire net, and the filtered matter was returned to the reaction vessel again, and 5.69 parts by mass of a 20% by mass potassium hydroxide aqueous solution (corresponding to a neutralization rate of 70 mol%) was dropped into the filtered matter while stirring it (replacement treatment). After the dropping was completed and the mixture was left to stand for 30 minutes, a neutralized water-containing water absorbent resin composition (regenerated water absorbent resin composition) was obtained.
[0244] The neutralized water-absorbent resin composition in a hydrated state (regenerated water-absorbent resin composition) was placed in a vacuum dryer adjusted to 60° C. and dried for 18 hours. Next, the dried product was pulverized using a vibration mill and further classified using JIS standard sieves with openings of 850 μm and 106 μm, thereby obtaining a water-absorbent resin composition precursor (13) having an average particle size of 360 μm that passed through the sieve with openings of 850 μm and remained on the sieve with openings of 106 μm.
[0245] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin composition precursor (13), and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0246] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (13). The obtained recycled water absorbent resin composition (13) contained a large amount of fibrous matter, and therefore had poor fluidity and was somewhat difficult to handle compared to the recycled water absorbent resin compositions (1) to (12).
[0247] [Comparative Example 1] The same operation as in Example 1 was performed except that the amount of 20 mass% potassium hydroxide aqueous solution used in the substitution treatment was changed from 1.54 mass parts to 7.19 mass parts (corresponding to a substitution rate of 70 mol%) in Example 1, to obtain a recycled water absorbent resin (C1). The physical properties of the recycled water absorbent resin (C1) are shown in Table 1.
[0248] [Comparative Example 2] The same operation as in Example 3 was carried out except that the amount of ammonium carbonate powder used in the substitution treatment was changed from 0.26 parts by mass to 1.24 parts by mass (corresponding to a substitution rate of 70 mol%) in Example 3, to obtain a recycled water absorbent resin (C2). The physical properties of the recycled water absorbent resin (C2) are shown in Table 1.
[0249] [Comparative Example 3] The water-absorbent resin (a) obtained in Production Example a was used as recycled water-absorbent resin (C3) as it was. The physical properties of the recycled water-absorbent resin (C3) are shown in Table 1.
[0250] [Comparative Example 4] A recycled water absorbent resin (C4) was obtained by carrying out the same operation as in Example 1, except that the replacement treatment in Example 1 was not carried out. Various physical properties of the recycled water absorbent resin (C4) are shown in Table 1.
[0251] [Comparative Example 5] 99.0 parts by mass of the water absorbent resin (a) (sodium hydroxide neutralization rate: 70 mol%) produced in Production Example a and 1.0 part by mass of pulp fiber (pulp fiber extracted from the absorbent part of a commercially available disposable diaper ("GOOON (registered trademark)" produced by Daio Paper Corporation) (fibrous material) were thoroughly mixed in a reaction vessel equipped with a stirrer to obtain a comparative water absorbent resin composition (C5).
[0252] [Comparative Example 6] In a reaction vessel equipped with a stirring device equipped with a stirring blade, 100 parts by mass of the simulated used water absorbent resin composition (b) (containing 3.19 parts by mass of water absorbent resin solid content) and 242 parts by mass of a 3.0 mass% aqueous citric acid solution were added and stirred for 15 minutes to perform an acid treatment. The simulated used water absorbent resin composition (b) after the acid treatment released more water than in the state before the treatment and was in a shrunk state (the acid treatment using the aqueous citric acid solution also served as a dehydration treatment).
[0253] The contents in the reaction vessel after the acid treatment were filtered through a 100 mesh (150 μm mesh) stainless steel wire mesh, and the filtered material was returned to the reaction vessel, and 323 parts by mass of deionized water was added thereto and stirred for 15 minutes.
[0254] Next, the content in the reaction vessel after the water washing treatment was filtered through a 100-mesh stainless steel wire net, and the filtered matter was placed in a vacuum dryer adjusted to 60°C without carrying out a replacement treatment, and dried for 18 hours. Next, the dried matter was pulverized using a vibration mill, and further classified through JIS standard sieves with openings of 850 μm and 106 μm, thereby obtaining a comparative water-absorbent resin composition precursor (C6) having an average particle size of 360 μm, which passed through the sieve with openings of 850 μm and remained on the sieve with openings of 106 μm.
[0255] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether (EGDGE), 1.35 parts by mass of propylene glycol, and 3.15 parts by weight of deionized water was uniformly mixed with 100 parts by mass of the obtained comparative water absorbent resin composition precursor (C6), and the mixture was subjected to heat treatment at 100° C. for 45 minutes.
[0256] Thereafter, the mixture was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a comparative recycled water absorbent resin composition (C6). The physical properties of the comparative recycled water absorbent resin composition (C6) are shown in Table 1.
[0257] Furthermore, the recycled water absorbent resins (1) to (5) and (C1) to (C4) were evaluated for plant growth according to the following method. The results are shown in Table 1. In Table 1, the cases where no treatment was carried out are indicated by "-".
[0258] Furthermore, the recycled water absorbent resin compositions (6) to (13) and (C5) to (C6) were evaluated for plant growth according to the following method. The results are shown in Table 2. In Table 2, the cases where no treatment was carried out are indicated by "-".
[0259] [Plant growth test (germination test)] 90 g of deionized water was added to 10 g of each recycled water absorbent resin or recycled water absorbent resin composition, and the recycled water absorbent resin or recycled water absorbent resin composition was allowed to stand for 1 hour to fully swell. Then, 35 g of the swollen recycled water absorbent resin or recycled water absorbent resin composition (hereinafter referred to as "swollen gel") was weighed out and placed in a plastic container with a capacity of 120 ml, and the bottom of the container was tapped to remove air.
[0260] Next, 10 radish sprouts were sown on the swollen gel, the plastic container was loosely covered with a lid, and the container was left at room temperature in the dark. After two days, the sprouts were visually observed to see if they had germinated. The germination rate (%) was calculated from the number of germinated seeds.
[0261] [Table 1]
[0262] [Table 2]
[0263] (summary) Table 1 shows the water-soluble content, residual monomer content, and deionized water CRC of the obtained recycled water absorbent resin, as well as the results of a plant growth test (germination rate) using the recycled water absorbent resin as a water retention material.
[0264] In the plant growth test, good results (germination rate) were obtained in Examples 1 to 5, but poorer results were obtained in Comparative Examples 1 to 4. These results show that when the substitution rate of potassium or nitrogen for the carboxyl group of the water absorbent resin is within an appropriate range, plant growth is good. Therefore, the recycled water absorbent resin and the recycled water absorbent resin according to the present invention are expected to be useful as water retention materials for plant growth.
[0265] The amount of water-soluble matter and the amount of residual monomer were significantly decreased in Examples 1 to 5 and Comparative Examples 1, 2, and 4, compared to the water-absorbent resin (a) that was not subjected to the substitution treatment. This result is considered to be due to the fact that when the moisture held in the simulated used water-absorbent resin (a) is released by the acid treatment (or the acid treatment and the dehydration treatment), the water-soluble matter and the residual monomer are simultaneously released from the water-absorbent resin. In addition, all of the deionized water CRCs showed values of 80 g / g or more except for Comparative Example 4, in which the substitution treatment was not performed during the regeneration treatment.
[0266] From these results, it can be said that the recycled water absorbent resin of the present invention is excellent in water absorbency and plant growth properties, has a low content of water-soluble matter and residual monomers, and is a water absorbent resin that takes safety to human skin into consideration.
[0267] Table 2 also shows the measurement results of the water-soluble content, residual monomer content, and deionized water CRC of the obtained recycled water absorbent resin composition, as well as the results of a plant growth test (germination rate) using the water absorbent resin composition as a water retention material.
[0268] In the plant growth test, good results (germination rate) were obtained in Examples 6 to 13, but poorer results were obtained in Comparative Examples 5 and 6. From these results and the results in Table 1, it is understood that by combining fibrous materials, good plant growth can be achieved with the water-absorbent resin in which the carboxyl group is substituted with potassium element or nitrogen element at a wider substitution rate. Therefore, the water-absorbent resin composition according to the present invention is also expected to be useful as a water-retaining material for plant growth.
[0269] The water-soluble content and the residual monomer content are significantly decreased in Examples 6 to 13 and Comparative Example 6, compared to the water-absorbent resin composition of Comparative Example 5, which was not subjected to the regeneration treatment. This is considered to be because the water-soluble content and the residual monomer are released from the water-absorbent resin when the water-absorbent resin in the simulated used water-absorbent resin composition releases moisture contained therein by the acid treatment and dehydration treatment carried out in the regeneration treatment process. In addition, the deionized water CRC showed a high value of 80 g / g or more in all cases except Comparative Example 6, which was not subjected to the replacement treatment during the regeneration treatment.
[0270] From these results, it can be said that the water-absorbent resin composition of the present invention is excellent in water absorbency and plant growth properties, has a low content of water-soluble matter and residual monomers, and is a composition that takes safety to human skin into consideration.
Claims
1. A raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salts, potassium salts, lithium salts, magnesium salts, calcium salts, and iron salts of a carboxyl group is treated with an acidic substance; a method for producing a regenerated water absorbent resin, comprising: adding a substance containing at least one element selected from the group consisting of potassium and nitrogen elements to the raw water absorbent resin treated with the acidic substance in an amount such that a substitution rate of the carboxyl groups is more than 5 mol % and less than 40 mol %, thereby substituting the carboxyl groups present in the raw water absorbent resin with the element.
2. The method according to claim 1, wherein the raw water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles or waste during a water absorbent resin manufacturing process.
3. The raw water absorbent resin is a recovered water absorbent resin recovered from a used absorbent article, the recovered water absorbent resin comprising a polymer having a sodium salt, a potassium salt, and / or a lithium salt of a carboxyl group, 2. The method according to claim 1, wherein the raw water absorbent resin is dehydrated and then treated with the acidic substance.
4. A method for producing a water-absorbing resin, comprising: producing a recycled water-absorbing resin by using the method according to any one of claims 1 to 3; and producing a water-absorbing resin by using the recycled water-absorbing resin as a part of a raw material.
5. A method for producing a water-retaining material, comprising producing a regenerated water-absorbent resin by using the method according to any one of claims 1 to 3.
6. A water-absorbent resin recycled from a used absorbent article or waste from a water-absorbent resin production process, the water-absorbent resin comprising a polymer having carboxyl groups and in which a portion of the carboxyl groups is substituted with at least one element selected from the group consisting of potassium and nitrogen.
7. 7. The recycled water absorbent resin according to claim 6, wherein the carboxyl groups of the polymer are substituted with potassium element at a substitution rate of more than 5 mol % and less than 40 mol %.
8. 7. The recycled water absorbent resin according to claim 6, wherein the carboxyl groups of the polymer are substituted with nitrogen elements at a substitution rate of more than 5 mol % and less than 40 mol %.
9. The polymer is a carboxyl group having an ammonium salt (—COONH) at a substitution rate of more than 5 mol % and less than 40 mol %. 4 7. The recycled water absorbent resin according to claim 6, wherein
10. The recycled water absorbent resin according to claim 6, wherein the water-soluble content is 20% by mass or less.
11. The recycled water absorbent resin according to claim 6, wherein the amount of residual monomer is 100 ppm by mass or less.
12. A water retention material comprising or consisting of the recycled water absorbent resin according to any one of claims 6 to 11.
13. A water-absorbent resin composition comprising: a water-absorbent resin having carboxyl groups, and a part of the carboxyl groups being substituted with at least one element selected from the group consisting of potassium element and nitrogen element at a substitution rate of 5 mol % or more and 100 mol % or less; and a fibrous material.
14. The water-absorbent resin composition according to claim 13, wherein the fibrous material is contained in an amount of 0.01 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the water-absorbent resin composition.
15. A water-retaining material comprising or consisting of the water-absorbent resin composition according to claim 13 or 14.
16. A raw water absorbent resin containing a polymer having at least one salt selected from the group consisting of sodium salts, lithium salts, magnesium salts, calcium salts, and iron salts of a carboxyl group is treated with an acidic substance; 14. The method for producing a water absorbent resin composition according to claim 13, comprising adding a substance containing at least one element selected from the group consisting of potassium element and nitrogen element to the raw water absorbent resin treated with the acidic substance in such an amount that a substitution rate of the carboxyl group is 5 mol % or more and 100 mol % or less, thereby substituting the carboxyl group present in the raw water absorbent resin with the element.
17. The method according to claim 16, wherein the raw water absorbent resin is a recovered water absorbent resin recovered from used absorbent articles or waste during a water absorbent resin manufacturing process.
Citation Information
Patent Citations
Water-retaining material
JP2021010303A